1983-2023 - Four decades Helicobacter pylori - what's next? 1983-2023 - Vierzig Jahre Helicobacter pylori - und nun? - Schulz, Christian; Schütte, Kerstin; Link, Alexander; Malfertheiner, Peter (Zeitschrift für Gastroenterologie, 2023)
Four decades ago the discovery of Helicobacter pylori was first reported in the international medical literature. Since then, there have been significant developments in basic and clinical science that have been translated into daily clinical practice. Changes in the management of H. pylori infection have occurred in diagnostic algorithms, indications for therapy and therapy itself. A special focus is directed to strategies of gastric cancer prevention. This manuscript briefly reviews the milestone in 40 years of H. pylori management.
CRIS-Team Scopus Importer:2025-10-13
Keywords: gastritis; Helicobacter pylori; stomach

Activation of Secretagogue Independent Gastric Acid Secretion via Endothelial Nitric Oxide Synthase Stimulation in Rats - Kitay, Alice Miriam; Link, Alexander; Geibel, John P. (Cellular Physiology and Biochemistry, 2017)
Background/Aims: L-arginine is an important mediator of cell division, wound healing, and immune function. It can be transformed by the nitric oxide synthase (NOS) to nitric oxide (NO), an important cell signaling molecule. Recent studies from our laboratory demonstrate specific effects of L-arginine (10mM) exposure on gastric acid secretion in rat parietal cells. Methods: Studies were performed with isolated gastric glands and the pH sensitive dye BCECF-AM +/- L-arginine to examine its effects on acid secretion. The direct NO-donor diethylamine NONOate sodium salt hydrate, was also used while monitoring intracellular pH. The specific inhibitor of the intracellular NO signal cascade ODQ was also used. Results: We found that gastric proton extrusion was activated with application of L-arginine (10mM), in a separate series when L-arginine (10mM) + L-NAME (30μM) were added there was no acid secretion. Addition of the NO-donor diethylamine NONOate sodium salt hydrate (10μM) also induced acid secretion. When the selective sGC-inhibitor ODQ was added with NONOate we did not observe acid secretion. Conclusion: We conclude that L-arginine is a novel secretagogue, which can mediate gastric acid secretion. Furthermore, the intake of L-arginine causes direct activation of the H + , K + ATPase and increased proton extrusion from parietal cells resulting in the increased risk for acid-related diseases. The NO/sGC/cGMP pathway has never been described as a possible intracellular mechanism for H + , K + ATPase activation before and presents a completely new scientific finding. Moreover, our studies demonstrate a novel role for L-NAME to effectively eliminate NOS induced acid secretion and thereby reducing the risk for L-arginine inducible ulcer disease.
CRIS-Team Scopus Importer:2025-10-13
Keywords: H; K; Nitric Oxide; PH; Reflux; Stomach

Altered Microbiota Diversity and Bile Acid Signaling in Cirrhotic and Noncirrhotic NASH-HCC - Sydor, Svenja; Best, Jan; Messerschmidt, Insa; Manka, Paul; Vilchez-Vargas, Ramiro; Brodesser, Susanne; Lucas, Christina; Wegehaupt, Annemarie; Wenning, Chiara; Aßmuth, Sophia; Hohenester, Simon; Link, Alexander; et al. (Clinical and Translational Gastroenterology, 2020)
OBJECTIVES: The precipitous increase in nonalcoholic steatohepatitis (NASH) is accompanied by a dramatic increase in the incidence of NASH-related hepatocellular carcinoma (HCC). HCC in NASH has a higher propensity to arise without pre-existing cirrhosis compared with other chronic liver diseases. METHODS: To identify the potential links between liver and gut in NASH-related hepatocarcinogenesis, we compared the gut microbiota and mediators of bile acid (BA) signaling in the absence or presence of cirrhosis through the analysis of stool and serum samples from patients with NASH non-HCC and NASH-HCC and healthy volunteers. RESULTS: Serum levels of total and individual BA were higher in NASH compared with healthy controls. Furthermore, serum levels of the primary conjugated BAs glycine-conjugated cholic acid, taurine-conjugated cholic acid, glycine-conjugated chenodeoxycholic acid, and taurine-conjugated chenodeoxycholic acid were significantly increased in cirrhotic vs noncirrhotic patients, independent of the occurrence of HCC. By contrast, serum FGF19 levels were higher in patients with NASH-HCC and associated with tumor markers as well as an attenuation of BA synthesis. Specific alterations in the gut microbiome were found for several bacteria involved in the BA metabolism including Bacteroides and Lactobacilli. Specifically, the abundance of Lactobacilli was associated with progressive disease, serum BA levels, and liver injury in NASH and NASH-HCC. DISCUSSION: Here, we demonstrate a clear association of the altered gut microbiota and primary conjugated BA composition in cirrhotic and noncirrhotic patients with NASH-HCC. Microbiota-associated alterations in BA homeostasis and farnesoid X receptor signaling, via FGF19, might thus contribute to fibrogenesis, liver injury, and tumorigenesis in NASH-HCC.
CRIS-Team Scopus Importer:2025-10-13

A Machine Learning Approach Towards Fatty Liver Disease Detection in Liver Ultrasound Images - Kuzhipathalil, Adarsh; Thomas, Anto; Chand, Keerthana; Gomes Ataide, Elmer Jeto; Link, Alexander; Niemann, Annika; Saalfeld, Sylvia; Friebe, Michael; Ziegle, Jens (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2025-10-13

Analysis of deregulated micrornas and their target genes in gastric cancer - Juzenas, Simonas; Salteniene, Violeta; Kupcinskas, Juozas; Link, Alexander; Kiudelis, Gediminas; Jonaitis, Laimas; Jarmalaite, Sonata; Kupcinskas, Limas; Malfertheiner, Peter; Skieceviciene, Jurgita (PLoS ONE, 2015)
Background: MicroRNAs (miRNAs) are widely studied non-coding RNAs that modulate gene expression. MiRNAs are deregulated in different tumors including gastric cancer (GC) and have potential diagnostic and prognostic implications. The aim of our study was to determine miRNA profile in GC tissues, followed by evaluation of deregulated miRNAs in plasma of GC patients. Using available databases and bioinformatics methods we also aimed to evaluate potential target genes of confirmed differentially expressed miRNA and validate these findings in GC tissues. Methods: The study included 51 GC patients and 51 controls. Initially, we screened miRNA expression profile in 13 tissue samples of GC and 12 normal gastric tissues with TaqMan low density array (TLDA). In the second stage, differentially expressed miRNAs were validated in a replication cohort using qRT-PCR in tissue and plasma samples. Subsequently, we analyzed potential target genes of deregulated miRNAs using bioinformatics approach, determined their expression in GC tissues and performed correlation analysis with targeting miRNAs. Results: Profiling with TLDA revealed 15 deregulated miRNAs in GC tissues compared to normal gastric mucosa. Replication analysis confirmed that miR-148a-3p, miR-204-5p, miR-223-3p and miR-375 were consistently deregulated in GC tissues. Analysis of GC patients' plasma samples showed significant down-regulation of miR-148a-3p, miR-375 and up-regulation of miR-223-3p compared to healthy subjects. Further, using bioinformatic tools we identified targets of replicated miRNAs and performed disease-associated gene enrichment analysis. Ultimately, we evaluated potential target gene BCL2 and DNMT3B expression by qRT-PCR in GC tissue, which correlated with targeting miRNA expression. Conclusions: Our study revealed miRNA profile in GC tissues and showed that miR-148a-3p, miR-223-3p and miR-375 are deregulated in GC plasma samples, but these circulating miRNAs showed relatively weak diagnostic performance as sole biomarkers. Target gene analysis demonstrated that BCL2 and DNMT3B expression in GC tissue correlated with their targeting miRNA expression.
CRIS-Team Scopus Importer:2025-10-13

Anti-TNFα treatment in Crohn’s disease: Impact on hepatic steatosis, gut-derived hormones and metabolic status - Manka, Paul; Sydor, Svenja; Wase, Nishikant; Best, Jan; Brandenburg, Malte; Hellbeck, Annika; Schänzer, Julia; Vilchez-Vargas, Ramiro; Link, Alexander; Figge, Anja; Jähnert, Andreas; von Arnim, Ulrike; et al. (Liver International, 2021)
Background and Aims: An association between Crohn's disease (CD) and hepatic steatosis has been reported. However, the underlying mechanisms of steatosis progression in CD are not clear. Among the most effective CD treatments are agents that inhibit Tumor-Necrosis-Factor (TNF) activity, yet it is unclear why anti-TNFα agents would affect steatosis in CD. Recent studies suggest that microbiome can affect both, CD and steatosis pathogenesis. Therefore, we here analysed a potential relationship between anti-TNF treatment and hepatic steatosis in CD, focusing on the gut-liver axis. Methods: This cross-sectional study evaluated patients with established CD, with and without anti-TNFα treatment, analysing serum markers of liver injury, measurement of transient elastography, controlled attenuation parameter (CAP) and MRI for fat detection. Changes in lipid and metabolic profiles were assessed by serum and stool lipidomics and metabolimics. Additionally, we analysed gut microbiota composition and mediators of bile acid (BA) signalling via stool and serum analysis. Results: Patients on anti-TNFα treatment had less hepatic steatosis as assessed by CAP and MRI. Serum FGF19 levels were significantly higher in patients on anti-TNFα therapy and associate with reduced steatosis and increased bowel motility. Neutral lipids including triglycerides were reduced in the serum of patients on anti-TNF treatment. Bacteria involved in BA metabolism and FGF19 regulation, including Firmicutes, showed group-specific alterations with low levels in patients without anti-TNFα treatment. Low abundance of Firmicutes was associated with higher triglyceride levels. Conclusions: Anti-TNFα treatment is associated with reduced steatosis, lower triglyceride levels, alterations in FXR-signalling (eg FGF19) and microbiota composition in CD.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Crohn's disease; microbiota; steatosis; TNF-alpha

A Potential Role for Bile Acid Signaling in Celiac Disease-Associated Fatty Liver - Manka, Paul; Sydor, Svenja; Schänzer-Ocklenburg, Julia M.; Brandenburg, Malte; Best, Jan; Vilchez-Vargas, Ramiro; Link, Alexander; Heider, Dominik; Brodesser, Susanne; Figge, Anja; Jähnert, Andreas; Coombes, Jason D.; et al. (Metabolites, 2022)
Celiac disease (CeD) is a chronic autoimmune disorder characterized by an intolerance to storage proteins of many grains. CeD is frequently associated with liver damage and steatosis. Bile acid (BA) signaling has been identified as an important mediator in gut–liver interaction and the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Here, we aimed to analyze BA signaling and liver injury in CeD patients. Therefore, we analyzed data of 20 CeD patients on a gluten-free diet compared to 20 healthy controls (HC). We furthermore analyzed transaminase levels, markers of cell death, BA, and fatty acid metabolism. Hepatic steatosis was determined via transient elastography, by MRI and non-invasive scores. In CeD, we observed an increase of the apoptosis marker M30 and more hepatic steatosis as compared to HC. Fibroblast growth factor 19 (FGF19) was repressed in CeD, while low levels were associated with steatosis, especially in patients with high levels of antitissue transglutaminase antibodies (anti-tTG). When comparing anti-tTG-positive CeD patients to individuals without detectable anti-tTG levels, hepatic steatosis was accentuated. CeD patients with significant sonographic steatosis (defined by CAP ≥ 283 db/m) were exclusively anti-tTG-positive. In summary, our results suggest that even in CeD patients in clinical remission under gluten-free diet, alterations in gut–liver axis, especially BA signaling, might contribute to steatotic liver injury and should be further addressed in future studies and clinical practice.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Bile acids; Celiac disease; FGF19; Hepatic steatosis; Non-alcoholic fatty liver disease (NAFLD)

Association of long non-coding rna polymorphisms with gastric cancer and atrophic gastritis - Petkevicius, Vytenis; Streleckiene, Greta; Balciute, Kotryna; Link, Alexander; Leja, Marcis; Malfertheiner, Peter; Skieceviciene, Jurgita; Kupcinskas, Juozas (Genes, 2020)
Long non-coding RNAs (lncRNA) play an important role in the carcinogenesis of various tumours, including gastric cancer. This study aimed to assess the associations of lncRNA ANRIL, H19, MALAT1, MEG3, HOTAIR single-nucleotide polymorphisms (SNPs) with gastric cancer and atrophic gastritis. SNPs were analyzed in 613 gastric cancer patients, 118 patients with atrophic gastritis and 476 controls from three tertiary centers in Germany, Lithuania and Latvia. Genomic DNA was extracted from peripheral blood leukocytes. SNPs were genotyped by the real-time polymerase chain reaction. Results showed that carriers of MALAT1 rs3200401 CT genotype had the significantly higher odds of atrophic gastritis than those with CC genotype (OR-1.81; 95% CI 1.17–2.80, p = 0.0066). Higher odds of AG were found in a recessive model (CC vs. TT + CT) for ANRIL rs1333045 (OR-1.88; 95% CI 1.19–2.95, p = 0.0066). Carriers of ANRIL (rs17694493) GG genotype had higher odds of gastric cancer (OR-4.93; 95% CI 1.28–19.00) and atrophic gastritis (OR-5.11; 95% CI 1.10–23.80) compared with the CC genotype, and carriers of HOTAIR rs17840857 TG genotype had higher odds of atrophic gastritis (OR-1.61 95% CI 1.04–2.50) compared with the TT genotype; however, the ORs did not reach the adjusted significance threshold (p < 0.007). In summary, our data provide novel evidence for a possible link between lncRNA SNPs and premalignant condition of gastric cancer, suggesting the involvement of lncRNAs in gastric cancer development.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Atrophic gastritis; Gastric cancer; Long non-coding RNA; Single-nucleotide polymorphism

Atrophic gastritis and gastric cancer tissue miRNome analysis reveals hsa-miR-129-1 and hsa-miR-196a as potential early diagnostic biomarkers - Varkalaite, Greta; Vaitkeviciute, Evelina; Inciuraite, Ruta; Salteniene, Violeta; Juzenas, Simonas; Petkevicius, Vytenis; Gudaityte, Rita; Mickevicius, Antanas; Link, Alexander; Kupcinskas, Limas; Leja, Marcis; Kupcinskas, Juozas; et al. (World Journal of Gastroenterology, 2022)
BACKGROUND Gastric cancer (GC) is one of the most frequently diagnosed tumor globally. In most cases, GC develops in a stepwise manner from chronic gastritis or atrophic gastritis (AG) to cancer. One of the major issues in clinical settings of GC is diagnosis at advanced disease stages resulting in poor prognosis. MicroRNAs (miRNAs) are small noncoding molecules that play an essential role in a variety of fundamental biological processes. However, clinical potential of miRNA profiling in the gastric cancerogenesis, especially in premalignant GC cases, remains unclear. AIM To evaluate the AG and GC tissue miRNomes and identify specific miRNAs’ potential for clinical applications (e.g., non-invasive diagnostics). METHODS Study included a total of 125 subjects: Controls (CON), AG, and GC patients. All study subjects were recruited at the Departments of Surgery or Gastroenterology, Hospital of Lithuanian University of Health Sciences and divided into the profiling (n = 60) and validation (n = 65) cohorts. Total RNA isolated from tissue samples was used for preparation of small RNA sequencing libraries and profiled using next-generation sequencing (NGS). Based on NGS data, deregulated miRNAs hsa-miR-129-1-3p and hsa-miR-196a-5p were analyzed in plasma samples of independent cohort consisting of CON, AG, and GC patients. Expression level of hsa-miR-129-1-3p and hsa-miR-196a-5p was determined using the quantitative real-time polymerase chain reaction and 2-ΔΔCt method. RESULTS Results of tissue analysis revealed 20 differentially expressed miRNAs in AG group compared to CON group, 129 deregulated miRNAs in GC compared to CON, and 99 altered miRNAs comparing GC and AG groups. Only 2 miRNAs (hsa-miR-129-1-3p and hsa-miR-196a-5p) were identified to be step-wise deregulated in healthy-premalignant-malignant sequence. Area under the curve (AUC)-receiver operating characteristic analysis revealed that expression level of hsa-miR-196a-5p is significant for discrimination of CON vs AG, CON vs GC and AG vs GC and resulted in AUCs: 88.0%, 93.1% and 66.3%, respectively. Comparing results in tissue and plasma samples, hsa-miR-129-1-3p was significantly down-regulated in GC compared to AG (P = 0.0021 and P = 0.024, tissue and plasma, respectively). Moreover, analysis revealed that hsa-miR-215-3p/5p and hsa-miR-934 were significantly deregulated in GC based on Helicobacter pylori (H. pylori) infection status [log2 fold change (FC) = -4.52, P-adjusted = 0.02; log2FC = - 4.00, P-adjusted = 0.02; log2FC = 6.09, P-adjusted = 0.02, respectively]. CONCLUSION Comprehensive miRNome study provides evidence for gradual deregulation of hsa-miR-196a-5p and hsa-miR-129-1-3p in gastric carcinogenesis and found hsamiR-215-3p/5p and hsa-miR-934 to be significantly deregulated in H. pylori carrying GC patients.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Atrophic gastritis; Biomarkers; Gastric cancer; Helicobacter pylori; MicroRNAs; Tumorigenesis

Biological removal processes in aerobic granular sludge for treating synthetic hospital wastewater: Effect of temperature - Muñoz-Palazon, Barbara; Rosa-Masegosa, Aurora; Vilchez-Vargas, Ramiro; Link, Alexander; Gorrasi, Susanna; Gonzalez-Lopez, Jesus; Gonzalez-Martinez, Alejandro (Journal of Water Process Engineering, 2022)
Four aerobic granular sludge reactors operated in sequential batch mode were implemented to understand the effect of low (7 °C) and high (26 °C) temperature in the removal of pharmaceuticals in the treated effluent. The chemical oxygen demand and nitrogen removal ratio were affected during the startup period in reactors feeding with drugs, but systems reached steady stability, achieving similar values in terms of biodegradation processes. Pharmaceuticals were progressively being removed from the effluent at high temperature, while at low temperature, oscillations in results were obtained. Naproxen was the most recalcitrant compound and trimethoprim accomplished the better removal ratios for both temperatures. The microbial community was completely dependent on operational temperature, although the proliferation of specific OTUs, Flavobacterium and Leadbetterella, was detected in reactors amendment with drugs. The metabolically active bacteria community showed lower diversity than total community. The statistical analyses corroborated that the effect of the temperature on the microbial community was more decisive than the treatment of pharmaceuticals.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Active microbial community; Aerobic granular sludge; Bacterial community; Pharmaceuticals; Temperature

Biopsy Sampling in Upper Gastrointestinal Endoscopy: A Survey from 10 Tertiary Referral Centres across Europe - Bornschein, Jan; Tran-Nguyen, Terry; Fernandez-Esparrach, Gloria; Ash, Stephen; Balaguer, Francesc; Bird-Lieberman, Elisabeth L.; Córdova, Henry; Dzerve, Zane; Fassan, Matteo; Leja, Marcis; Lyutakov, Ivan; Middelburg, Tim; et al. (Digestive Diseases, 2021)
Background: Guidelines give robust recommendations on which biopsies should be taken when there is endoscopic suggestion of gastric inflammation. Adherence to these guidelines often seems arbitrary. This study aimed to give an overview on current practice in tertiary referral centres across Europe. Methods: Data were collected at 10 tertiary referral centres. Demographic data, the indication for each procedure, endoscopic findings, and the number and sampling site of biopsies were recorded. Findings were compared between centres, and factors influencing the decision to take biopsies were explored. Results: Biopsies were taken in 56.6% of 9,425 procedures, with significant variation between centres (p < 0.001). Gastric biopsies were taken in 43.8% of all procedures. Sampling location varied with the procedure indication (p < 0.001) without consistent pattern across the centres. Fewer biopsies were taken in centres which routinely applied the updated Sydney classification for gastritis assessment (46.0%), compared to centres where this was done only upon request (75.3%, p < 0.001). This was the same for centres stratifying patients according to the OLGA system (51.8 vs. 73.0%, p < 0.001). More biopsies were taken in centres following the MAPS guidelines on stomach surveillance (68.1 vs. 37.1%, p < 0.001). Biopsy sampling was more likely in younger patients in 8 centres (p < 0.05), but this was not true for the whole cohort (p = 0.537). The percentage of procedures with biopsies correlated directly with additional costs charged in case of biopsies (r = 0.709, p = 0.022). Conclusion: Adherence to guideline recommendations for biopsy sampling at gastroscopy was inconsistent across the participating centres. Our data suggest that centre-specific policies are applied instead.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biopsy sampling; CLO test; Gastritis; Gastroscopy; MAPS; OLGA; Sydney

Blue Light Imaging and Linked Color Imaging for the Characterization of Mucosal Changes in Chronic Gastritis: A Clinicians View and Brief Technical Report - Weigt, Jochen; Malfertheiner, Peter; Canbay, Ali; Haybaeck, Johannes; Bird-Lieberman, Elizabeth; Link, Alexander (Digestive Diseases, 2020)
Background: Blue light imaging (BLI) and linked color imaging (LCI) are new imaging modalities for the endoscopic evaluation of mucosal changes within the digestive tract. There is little experience with these modalities in the characterization of chronic gastritis (CG) intestinal metaplasia (IM) and atrophy in the stomach. Aims and Methods: In a single-center observational pilot study, we correlated endoscopic findings with histology in selected patients. Results: Findings from 29 patients were included in the analysis. Six patients had macroscopically normal gastric mucosa at endoscopy, and this was confirmed histologically in 5 of them. At endoscopy, 15 patients had the presence of IM in the antrum predicted, and this was confirmed histologically in 11 (73%). In the corpus, we predicted the presence of IM in 14 patients, and this was confirmed in 11 (78%) at histology. Eleven patients had the endoscopic suspicion of atrophy in antrum, which was confirmed in 9 patients (82%). In total, 14 patients had endoscopic suspicion of atrophy in corpus mucosa at endoscopy, but only 10 were confirmed in histology (71%). The concordance of endoscopic classification and histology was 93% for antrum and 88% for corpus. The positive predictive value and negative predictive value for IM were 0.74 and 0.83 and for atrophy 0.63 and 0.97, respectively. Conclusions: LCI and BLI are helpful in characterization of mucosal changes in CG. The ability to rule out premalignant conditions by endoscopy only reflects the clinical use and harbors significant clinical implications.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Atrophic gastritis; Blue light imaging; Chronic gastritis; Intestinal metaplasia; Linked color imaging

Characterization of Maladaptive Processes in Acute, Chronic and Remission Phases of Experimental Colitis in C57BL/6 Mice - Gelmez, Elif; Lehr, Konrad; Kershaw, Olivia; Frentzel, Sarah; Vilchez-Vargas, Ramiro; Bank, Ute; Link, Alexander; Schüler, Thomas; Jeron, Andreas; Bruder, Dunja (Biomedicines, 2022)
Inflammatory bowel disease (IBD) is a chronic recurrent inflammatory disease with unknown etiology. Dextran sulfate sodium (DSS) induced colitis is a widely used mouse model in IBD research. DSS colitis involves activation of the submucosal immune system and can be used to study IBD-like disease characteristics in acute, chronic, remission and transition phases. Insight into colon inflammatory parameters is needed to understand potentially irreversible adaptations to the chronification of colitis, determining the baseline and impact of further inflammatory episodes. We performed analyses of non-invasive and invasive colitis parameters in acute, chronic and remission phases of the DSS colitis in C57BL/6 mice. Non-invasive colitis parameters poorly reflected inflammatory aspects of colitis in chronic remission phase. We found invasive inflammatory parameters, positively linked to repeated DSS-episodes, such as specific colon weight, inflamed colon area, spleen weight, absolute cell numbers of CD4+ and CD8+ T cells as well as B cells, blood IFN-γ level, colonic chemokines BLC and MDC as well as the prevalence of Turicibacter species in feces. Moreover, microbial Lactobacillus species decreased with chronification of disease. Our data point out indicative parameters of recurrent gut inflammation in context of DSS colitis.
CRIS-Team Scopus Importer:2025-10-13
Keywords: colon; colon inflammatory milieu; DSS colitis; intestinal microbiome; lamina propria leukocytes

Circulating and fecal microRNAs as biomarkers for inflammatory bowel diseases - Schönauen, Katharina; Le, Nha; Von Arnim, Ulrike; Schulz, Christian; Malfertheiner, Peter; Link, Alexander (Inflammatory Bowel Diseases, 2018)
Background: Assessment of the disease activity in inflammatory bowel disease (IBD) is essential for adequate treatment management and reliable noninvasive biomarkers for verification of mucosal healing are still needed. MicroRNAs (miRNAs) are differentially expressed in IBD and cancer. We aimed to evaluate the potential of circulating and fecal miRNAs as diagnostic biomarkers for IBD. Methods: In this proof-of-principle study we used 2 independent patient cohorts. Testing cohort (n = 96) included serum and fecal samples from controls (n = 35) and IBD patients (n = 61) including 43 patients with Crohn's disease (CD), 18 with ulcerative colitis (UC) with an active disease (n = 38), or in remission (n = 23). Validation cohort included fecal samples from patients with calprotectin/endoscopy-confirmed active disease (n = 30) or in remission (n = 15). Target-based approach (miR-16, miR-21, miR-155, and miR-223) has been used to evaluate miRNA expression. Results: Sera samples from IBD patients showed higher level of miR-16, miR-21, and miR-223, but not miR-155, compared to controls and was higher in CD than in UC patients. Much stronger miRNA expression changes were observed in feces from IBD patients for all studied miRNAs with highest expression of miR-155 and miR-223 in testing and validation cohorts. MiRNA expression correlated with clinical remission, however, only fecal but not circulating miRNAs, correlated with surrogate parameters such as fecal calprotectin or C-reactive protein. Conclusions: Our data provide a novel evidence for differential expression level of fecal miRNAs in IBD. We demonstrate that miRNAs in feces correlate with disease activity and may be considered as potential tool for the further biomarker research in IBD.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biomarker; Crohn's disease; Feces; Inflammatory bowel disease; MicroRNA; Ulcerative colitis

Circulating miR-21-5p level has limited prognostic value in patients with hepatocellular carcinoma and is influenced by renal function - Franck, Martin; Thon, Cosima; Schütte, Kerstin; Malfertheiner, Peter; Link, Alexander (World Journal of Hepatology, 2020)
BACKGROUND MicroRNAs (miRNAs) have been suggested as biomarkers for malignant diseases including hepatocellular carcinoma (HCC). Specifically, hsa-miR-21-5p (miR-21) is among the most frequently deregulated miRNA in cancer. The diagnostic and prognostic value of miR-21 has been demonstrated in HCC tissue, mostly in the Asian population. Although the impact of various factors has been recently reported for circulating hsa-miR-122-5p (miR-122), at present only limited knowledge is available for miR-21. AIMTo evaluate the value of miR-21 for the assessment of prognosis in HCC patients and to delineate the influence of clinical and preanalytical factors on miR-21 level in sera. METHODS Patients with confirmed HCC from our European cohort with predominantly alcohol-associated liver damage were included in the study. All subjects were characterized according to their clinical and laboratory work-up and overall survival data were obtained. Quantitative real-time polymerase chain reaction was performed for miR-21 and spiked-in cel-miR-39-3p. The results were compared to previously reported miR-122 data. RESULTS Survival of HCC patients was comparable between patients with low and high serum miR-21 concentration. No association was observed between miR-21 level in sera and Child-Pugh score, Barcelona Clinic Liver Cancer staging system, or etiology of HCC/liver disease. Age, gender, or pretreatment had no association with miR-21 level. A positive correlation was observed between miR-21 and aspartate aminotransferase (r = 0.2854, P = 0.0061), serum miR-122 (r = 0.2624, P = 0.0120), and the International Normalized Ratio (r = 0.2065, P = 0.0496). Negative correlation of miR-21 with serum creatinine (r = -0.2215, P = 0.0348) suggests renal function as a potential influencing factor in miR-21 biogenesis in blood. CONCLUSION The results from this work do not support clinically relevant prognostic value of circulating miR-21 in HCC patients in real-life settings. Following systematic evaluation, we identified renal function and aspartate aminotransferase as potential factors that may affect miR-21 concentration in blood. This knowledge should be considered in future miRNA-based biomarker studies not only for HCC but also for other diseases.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Hepatocellular cancer; Hepatocellular carcinoma; MicroRNA; miR-21-5p; Prognosis; Renal function

Comparison of different microbiome analysis pipelines to validate their reproducibility of gastric mucosal microbiome composition - Lehr, Konrad; Oosterlinck, Baptiste; Then, Chee Kin; Gemmell, Matthew R.; Gedgaudas, Rolandas; Bornschein, Jan; Kupcinskas, Juozas; Smet, Annemieke; Hold, Georgina; Link, Alexander (mSystems, 2025)
Microbiome analysis has become a crucial tool for basic and translational research due to its potential for translation into clinical practice. However, there is ongoing controversy regarding the comparability of different bioinformatic analysis platforms and a lack of recognized standards, which might have an impact on the translational potential of results. This study investigates how the performance of different microbiome analysis platforms impacts the final results of mucosal microbiome signatures. Across five independent research groups, we compared three distinct and frequently used microbiome analysis bioinformatic packages (DADA2, MOTHUR, and QIIME2) on the same subset of fastQ files. The source data set encompassed 16S rRNA gene raw sequencing data (V1–V2) from gastric biopsy samples of clinically well-defined gastric cancer (GC) patients (n = 40; with and without Helicobacter pylori [H. pylori] infection) and controls (n = 39, with and without H. pylori infection). Independent of the applied protocol, H. pylori status, microbial diversity and relative bacterial abundance were reproducible across all platforms, although differences in performance were detected. Furthermore, alignment of the filtered sequences to the old and new taxonomic databases (i.e., Ribosomal Database Project, Greengenes, and SILVA) had only a limited impact on the taxonomic assignment and thus on global analytical outcomes. Taken together, our results clearly demonstrate that different microbiome analysis approaches from independent expert groups generate comparable results when applied to the same data set. This is crucial for interpreting respective studies and underscores the broader applicability of microbiome analysis in clinical research, provided that robust pipelines are utilized and thoroughly documented to ensure reproducibility.
CRIS-Team Scopus Importer:2025-10-13
Keywords: 16S rRNA gene sequencing; DADA2; gastric cancer; Helicobacter pylori; MOTHUR; pipeline comparison; QIIME2

Comparison of Fecal MicroRNA Isolation Using Various Total RNA Isolation Kits - Lederer, Theresa; Hipler, Noam M.; Thon, Cosima; Kupcinskas, Juozas; Link, Alexander (Genes, 2024)
Fecal specimens have long been regarded as promising sources for gastrointestinal cancer screening and have, thus, been extensively investigated in biomarker research. MicroRNAs (miRNAs) are small, non-coding RNA molecules involved in regulating various biological processes. They are commonly dysregulated during tumor development and exhibit differential expression in feces. To assess the preanalytical feasibility of fecal miRNA analysis, we systematically compared the performance of commonly used total RNA extraction methods. Fecal samples from healthy subjects were utilized for this evaluation. Various methods, including miRNeasy, Universal, Trizol, RNeasy, and mirVana kits, were employed to isolate total RNA. MiRNA expression analyses were conducted using TaqMan or SYBR Green qRT-PCR for a subset of miRNAs, with externally spiked-in cel-miR-39 used for normalization. Most methods demonstrated similar performance in terms of the total RNA concentration and purity. Externally spiked cel-miR-39 and endogenous miRNAs (RNU6b, miR-16, and miR-21) exhibited comparable concentrations across the different RNA isolation methods, whereas the RNeasy mini kit consistently yielded lower values. Our findings suggest that various isolation methods produce reproducible and comparable miRNA expression results, supporting the potential comparability and translational applicability of miRNA-based biomarker research in the future.
CRIS-Team Scopus Importer:2025-10-13
Keywords: fecal biomarker; microRNA; microRNA kits; total RNA

Comparison of genomic and transcriptional microbiome analysis in gastric cancer patients and healthy individuals - Nikitina, Darja; Lehr, Konrad; Vilchez-Vargas, Ramiro; Jonaitis, Laimas Virginijus; Urba, Mindaugas; Kupcinskas, Juozas; Skieceviciene, Jurgita; Link, Alexander (World Journal of Gastroenterology, 2023)
BACKGROUND Helicobacter pylori and the stomach microbiome play a crucial role in gastric carcinogenesis, and detailed characterization of the microbiome is necessary for a better understanding of the pathophysiology of the disease. There are two common modalities for microbiome analysis: DNA (16S rRNA gene) and RNA (16S rRNA transcript) sequencing. The implications from the use of one or another sequencing approach on the characterization and comparability of the mucosal microbiome in gastric cancer (GC) are poorly studied. AIM To characterize the microbiota of GC using 16S rRNA gene and its transcript and determine difference in the bacterial composition. METHODS In this study, 316 DNA and RNA samples extracted from 105 individual stomach biopsies were included. The study cohort consisted of 29 healthy control individuals and 76 patients with GC. Gastric tissue biopsy samples were collected from damaged mucosa and healthy mucosa at least 5 cm from the tumor tissue. From the controls, healthy stomach mucosa biopsies were collected. From all biopsies RNA and DNA were extracted. RNA was reverse transcribed into cDNA. V1-V2 region of bacterial 16S rRNA gene from all samples were amplified and sequenced on an Illumina MiSeq platform. Bray-Curtis algorithm was used to construct sample-similarity matrices abundances of taxonomic ranks in each sample type. For significant differences between groups permutational multivariate analysis of variance and Mann-Whitney test followed by false-discovery rate test were used. RESULTS Microbial analysis revealed that only a portion of phylotypes (18%-30%) overlapped between microbial profiles obtained from DNA and RNA samples. Detailed analysis revealed differences between GC and controls depending on the chosen modality, identifying 17 genera at the DNA level and 27 genera at the RNA level. Ten of those bacteria were found to be different from the control group at both levels. The key taxa showed congruent results in various tests used; however, differences in 7 bacteria taxa were found uniquely only at the DNA level, and 17 uniquely only at the RNA level. Furthermore, RNA sequencing was more sensitive for detecting differences in bacterial richness, as well as differences in the relative abundance of Reyranella and Sediminibacterium according to the type of GC. In each study group (control, tumor, and tumor adjacent) were found differences between DNA and RNA bacterial profiles. CONCLUSION Comprehensive microbial study provides evidence for the effect of choice of sequencing modality on the microbiota profile, as well as on the identified differences between case and control.
CRIS-Team Scopus Importer:2025-10-13
Keywords: 16S rDNA; 16S rRNA gene; 16S rRNA transcript; Gastric cancer; Helicobacter pylori; Microbiome

Constituents of stable commensal microbiota imply diverse colonic epithelial cell reactivity in patients with ulcerative colitis - Inciuraite, Ruta; Gedgaudas, Rolandas; Lukosevicius, Rokas; Tilinde, Deimante; Ramonaite, Rima; Link, Alexander; Kasetiene, Neringa; Malakauskas, Mindaugas; Kiudelis, Gediminas; Jonaitis, Laimas Virginijus; Kupcinskas, Juozas; Juzenas, Simonas; et al. (Gut Pathogens, 2024)
Background: Despite extensive research on microbiome alterations in ulcerative colitis (UC), the role of the constituent stable microbiota remains unclear. Results: This study, employing 16S rRNA-gene sequencing, uncovers a persistent microbial imbalance in both active and quiescent UC patients compared to healthy controls. Using co-occurrence and differential abundance analysis, the study highlights microbial constituents, featuring Phocaeicola, Collinsella, Roseburia, Holdemanella, and Bacteroides, that are not affected during the course of UC. Co-cultivation experiments, utilizing commensal Escherichia coli and Phocaeicola vulgatus, were conducted with intestinal epithelial organoids derived from active UC patients and controls. These experiments reveal a tendency for a differential response in tight junction formation and maintenance in colonic epithelial cells, without inducing pathogen recognition and stress responses, offering further insights into the roles of these microorganisms in UC pathogenesis. These experiments also uncover high variation in patients’ response to the same bacteria, which indicate the need for more comprehensive, stratified analyses with an expanded sample size. Conclusion: This study reveals that a substantial part of the gut microbiota remains stable throughout progression of UC. Functional experiments suggest that members of core microbiota – Escherichia coli and Phocaeicola vulgatus – potentially differentially regulate the expression of tight junction gene in the colonic epithelium of UC patients and healthy individuals.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Colonic epithelial barrier; Colonic epithelial organoids; Crosstalk; Escherichia coli; Gut microbiota; Phocaeicola vulgatus; Ulcerative colitis

Contrast-Enhanced Ultrasound Algorithms (CEUS-LIRADS/ESCULAP) for the Noninvasive Diagnosis of Hepatocellular Carcinoma – A Prospective Multicenter DEGUM Study - Schellhaas, Barbara; Bernatik, Thomas; Bohle, Wolfram; Borowitzka, Fanny; Chang, Johannes; Dietrich, Christoph F.; Dirks, Klaus; Donoval, Robert; Drube, Kristine; Friedrich-Rust, Mireen; Gall, Christine; Gittinger, Fleur; et al. (Ultraschall in der Medizin, 2020)
Background This prospective multicenter study funded by the DEGUM assesses the diagnostic accuracy of standardized contrast-enhanced ultrasound (CEUS) for the noninvasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. Methods Patients at high risk for HCC with a histologically proven focal liver lesion on B-mode ultrasound were recruited prospectively in a multicenter approach. Clinical and imaging data were entered via online entry forms. The diagnostic accuracies for the noninvasive diagnosis of HCC were compared for the conventional interpretation of standardized CEUS at the time of the examination (= CEUS on-site) and the two CEUS algorithms ESCULAP (Erlanger Synopsis for Contrast-enhanced Ultrasound for Liver lesion Assessment in Patients at risk) and CEUS LI-RADS (Contrast-Enhanced UltraSound Liver Imaging Reporting and Data System). Results 321 patients were recruited in 43 centers; 299 (93.1 %) had liver cirrhosis. The diagnosis according to histology was HCC in 256 cases, and intrahepatic cholangiocarcinoma (iCCA) in 23 cases. In the subgroup of cirrhotic patients (n = 299), the highest sensitivity for the diagnosis of HCC was achieved with the CEUS algorithm ESCULAP (94.2 %) and CEUS on-site (90.9 %). The lowest sensitivity was reached with the CEUS LI-RADS algorithm (64 %; p < 0.001). However, the specificity of CEUS LI-RADS (78.9 %) was superior to that of ESCULAP (50.9 %) and CEUS on-site (64.9 %; p < 0.001). At the same time, the negative predictive value (NPV) of CEUS LI-RADS was significantly inferior to that of ESCULAP (34.1 % vs. 67.4 %; p < 0.001) and CEUS on-site (62.7 %; p < 0.001). The positive predictive values of all modalities were high (around 90 %), with the best results seen for CEUS LI-RADS and CEUS on-site. Conclusion This is the first multicenter, prospective comparison of standardized CEUS and the recently developed CEUS-based algorithms in histologically proven liver lesions in cirrhotic patients. Our results reaffirm the excellent diagnostic accuracy of CEUS for the noninvasive diagnosis of HCC in high-risk patients. However, on-site diagnosis by an experienced examiner achieves an almost equal diagnostic accuracy compared to CEUS-based diagnostic algorithms.
CRIS-Team Scopus Importer:2020-10-16
Keywords: CEUS algorithms; CEUS LI-RADS (Contrast-Enhanced UltraSound Liver Imaging Reporting and Data System); Contrast-enhanced ultrasound (CEUS); ESCULAP; Hepatocellular carcinoma

Curcumin Modulates DNA Methylation in Colorectal Cancer Cells - Link, Alexander; Balaguer, Francesc; Shen, Yan; Lozano, Juan Jose; Leung, Hon Chiu E.; Boland, C. Richard; Goel, Ajay (PLoS ONE, 2013)
Aim: Recent evidence suggests that several dietary polyphenols may exert their chemopreventive effect through epigenetic modifications. Curcumin is one of the most widely studied dietary chemopreventive agents for colon cancer prevention, however, its effects on epigenetic alterations, particularly DNA methylation, remain unclear. Using systematic genome-wide approaches, we aimed to elucidate the effect of curcumin on DNA methylation alterations in colorectal cancer cells. Materials and Methods: To evaluate the effect of curcumin on DNA methylation, three CRC cell lines, HCT116, HT29 and RKO, were treated with curcumin. 5-aza-2′-deoxycytidine (5-aza-CdR) and trichostatin A treated cells were used as positive and negative controls for DNA methylation changes, respectively. Methylation status of LINE-1 repeat elements, DNA promoter methylation microarrays and gene expression arrays were used to assess global methylation and gene expression changes. Validation was performed using independent microarrays, quantitative bisulfite pyrosequencing, and qPCR. Results: As expected, genome-wide methylation microarrays revealed significant DNA hypomethylation in 5-aza-CdR-treated cells (mean β-values of 0.12), however, non-significant changes in mean β-values were observed in curcumin-treated cells. In comparison to mock-treated cells, curcumin-induced DNA methylation alterations occurred in a time-dependent manner. In contrast to the generalized, non-specific global hypomethylation observed with 5-aza-CdR, curcumin treatment resulted in methylation changes at selected, partially-methylated loci, instead of fully-methylated CpG sites. DNA methylation alterations were supported by corresponding changes in gene expression at both up- and down-regulated genes in various CRC cell lines. Conclusions: Our data provide previously unrecognized evidence for curcumin-mediated DNA methylation alterations as a potential mechanism of colon cancer chemoprevention. In contrast to non-specific global hypomethylation induced by 5-aza-CdR, curcumin-induced methylation changes occurred only in a subset of partially-methylated genes, which provides additional mechanistic insights into the potent chemopreventive effect of this dietary nutraceutical. © 2013 Link et al.
CRIS-Team Scopus Importer:2025-10-13

Current biomarkers for hepatocellular carcinoma: Surveillance, diagnosis and prediction of prognosis - Schütte, Kerstin; Schulz, Christian; Link, Alexander; Malfertheiner, Peter (World Journal of Hepatology, 2015)
Biomarkers for surveillance, diagnosis and prediction of prognosis in patients with hepatocellular carcinoma (HCC) are currently not ready for introduction into clinical practice because of limited sensitivity and specificity. Especially for the early detection of small HCC novel biomarkers are needed to improve the current effectiveness of screening performed by ultrasound. The use of high-throughput technologies in hepatocellular research allows to identify molecules involved in the complex pathways in hepatocarcinogenesis. Several invasive and non-invasive biomarkers have been identified already and have been evaluated in different clinical settings. Gene signatures with prognostic potential have been identified by gene expression profiling from tumor tissue. However, a single "all-in-one" biomarker that fits all-surveillance, diagnosis, prediction of prognosis-has not been found so far. The future of biomarkers most probably lies in a combination of non-invasive biomarkers, imaging and clinical parameters in a surveillance setting. Molecular profiling of tumorous and non-tumorous liver tissue may allow a prediction of prognosis for the individual patient and hopefully clear the way for individual treatment approaches. This article gives an overview on current developments in biomarker research in HCC with a focus on currently available and novel biomarkers, in particular on microRNA.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biomarker; Diagnosis; Hepatocellular carcinoma; MicroRNA; Prognosis

Differential Expression of Long Noncoding RNA HOTAIR in Intestinal Metaplasia and Gastric Cancer - Petkevicius, Vytenis; Thon, Cosima; Steponaitiene, Ruta; Skieceviciene, Jurgita; Janciauskas, Dainius; Jechorek, Doerthe; Malfertheiner, Peter; Kupcinskas, Juozas; Link, Alexander (Clinical and Translational Gastroenterology, 2022)
INTRODUCTION: High expression of HOTAIR promotes tumor growth and carries a dismal prognosis for the patient. We investigated the prognostic value of HOTAIR expression in gastric cancer (GC) and systematically delineate the expression in relation to Helicobacter pylori infection and preneoplastic changes. METHODS: HOTAIR expression was analyzed in surgical paired tissue samples of patients with GC and biopsy samples from patients with atrophic gastritis and/or intestinal metaplasia (AG 6 -IM), chronic nonatrophic gastritis, and controls. The cancer genome atlas (TCGA) data were used for validation. HOTAIR expression was evaluated in sera and ascites of patients with GC. Quantitative HOTAIR expression analysis was performed using quantitative polymerase chain reaction, and LINE-1 methylation was assessed by bisulfite pyrosequencing. RESULTS: HOTAIR was more frequently detected in tumor tissues compared with adjacent gastric mucosa (65.4% vs 8.6%). HOTAIR expression was associated with depth of tumor invasion and tumor location and with shorter overall survival in patients with diffuse-type GC as confirmed in the TCGA cohort. HOTAIR was not detectable in controls but was found in 2.2% of patients with chronic nonatrophic gastritis and 18.3% of patients with AG 6 IM, which was further associated with IM, grade of IM, and H. pylori positivity. DISCUSSION: HOTAIR expression was associated with GC and preneoplastic changes of stomach mucosa. Although HOTAIR expression was strongly linked to IM, HOTAIR expression was only associated with worse prognosis in Lauren diffuse and not intestinal type of GC. Further studies are needed to evaluate the value of HOTAIR as diagnostic and predictive biomarker in IM and translational therapeutic relevance of HOTAIR in diffuse-type GC.
CRIS-Team Scopus Importer:2025-10-13

Differential expression of microRNAs in preneoplastic gastric mucosa - Link, Alexander; Schirrmeister, Wiebke; Langner, Cosima; Varbanova, Mariya; Bornschein, Jan; Wex, Thomas; Malfertheiner, Peter (Scientific Reports, 2015)
Gastric carcinogenesis is a multifactorial H.pylori-triggered dynamic process that goes through a cascade of preneoplastic conditions. The expression of miRNAs in the stomach with regard to preneoplastic precursor conditions and H.pylori infection has not been investigated systematically. In this prospective proof-of-principle study, we evaluated the miRNA expression in gastric antrum and corpus mucosa from patients with chronic non-atrophic gastritis (CNAG), atrophic gastritis (AG), and GC compared to controls. Gastric normal mucosa shows a unique expression pattern for miR-21, miR-155 and miR-223, which is specific for different regions. In correlation with progression of Correa's cascade and H.pylori infection, we observed a gradual increase in miR-155 and miR-223 both in corpus and antrum and miR-21 only in the antrum mucosa. Using miRNA expression we calculated a score that allowed us to discriminate patients with AG from subjects with normal mucosa with high diagnostic accuracy in testing and validation cohorts reproducibly. In summary, the expression pattern of miRNAs in the gastric mucosa is gradually increased with progression of Correa's cascade and H.pylori infection, suggesting miRNAs as potential biomarkers for preneoplastic precursor conditions. However, differences of miRNA expression between the gastric antrum and the corpus need to be considered in future studies.
CRIS-Team Scopus Importer:2025-10-13

DNA methylation in human gastric epithelial cells defines regional identity without restricting lineage plasticity - Fritsche, Kristin; Boccellato, Francesco; Schlaermann, Philipp; Koeppel, Max; Denecke, Christian; Link, Alexander; Malfertheiner, Peter; Gut, Ivo; Meyer, Thomas F.; Berger, Hilmar (Clinical Epigenetics, 2022)
Background: Epigenetic modifications in mammalian DNA are commonly manifested by DNA methylation. In the stomach, altered DNA methylation patterns have been observed following chronic Helicobacter pylori infections and in gastric cancer. In the context of epigenetic regulation, the regional nature of the stomach has been rarely considered in detail. Results: Here, we establish gastric mucosa derived primary cell cultures as a reliable source of native human epithelium. We describe the DNA methylation landscape across the phenotypically different regions of the healthy human stomach, i.e., antrum, corpus, fundus together with the corresponding transcriptomes. We show that stable regional DNA methylation differences translate to a limited extent into regulation of the transcriptomic phenotype, indicating a largely permissive epigenetic regulation. We identify a small number of transcription factors with novel region-specific activity and likely epigenetic impact in the stomach, including GATA4, IRX5, IRX2, PDX1 and CDX2. Detailed analysis of the Wnt pathway reveals differential regulation along the craniocaudal axis, which involves non-canonical Wnt signaling in determining cell fate in the proximal stomach. By extending our analysis to pre-neoplastic lesions and gastric cancers, we conclude that epigenetic dysregulation characterizes intestinal metaplasia as a founding basis for functional changes in gastric cancer. We present insights into the dynamics of DNA methylation across anatomical regions of the healthy stomach and patterns of its change in disease. Finally, our study provides a well-defined resource of regional stomach transcription and epigenetics.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Epigenetic regulation; Gastric cancer; Gastric epithelial development; Human stomach; Intestinal metaplasia

Donated stool for faecal microbiota transplantation is not a drug, but guidance and regulation are needed - Keller, Josbert J.; Vehreschild, Maria J.G.T.; Hvas, Christian L.; Jørgensen, Simon M.D.; Kupcinskas, Juozas; Link, Alexander; Mulder, Chris J.J.; Goldenberg, Simon D.; Arasaradnam, Ramesh; Sokol, Harry; Gasbarrini, Antonio; Hoegenauer, Christoph; et al. (United European Gastroenterology Journal, 2020)
CRIS-Team Scopus Importer:2025-10-13

Effect of a 24-week supervised concurrent exercise intervention on fecal microbiota diversity and composition in young sedentary adults: The ACTIBATE randomized controlled trial - Martinez-Tellez, Borja; Xu, Huiwen; Ortiz-Alvarez, Lourdes; Rodríguez-García, Carmen; Schönke, Milena; Jurado-Fasoli, Lucas; Osuna-Prieto, Francisco J.; Alcantara, Juan M.A.; Acosta, Francisco M.; Amaro-Gahete, Francisco J.; Folkerts, Gert; Vilchez-Vargas, Ramiro; et al. (Clinical Nutrition, 2025)
Background: Numerous physiological responses to exercise are observed in humans, yet the effects of long-term exercise and varying intensities on the diversity and composition of human fecal microbiota remain unclear. We investigated the effect of a 24-week supervised concurrent exercise intervention, at moderate and vigorous intensities, on fecal microbiota diversity and composition in young adults. Methods: This ancillary study was based on data from the ACTIBATE randomized controlled trial (ClinicalTrials.gov ID: NCT02365129), and included adults (aged 18–25 years, 70 % female) that were randomized to (i) a control group (CON: no exercise, n = 20), (ii) a moderate-intensity exercise group (MOD-EX, n = 21), and (iii) a vigorous-intensity exercise group (VIG-EX, n = 20). Fecal samples were collected before and after the 24-week exercise intervention, and the diversity and composition of the fecal microbiota were analyzed by 16S rRNA sequencing. Inferential functional profiling of the fecal microbiota was performed and correlations between microbial changes and cardiometabolic outcomes were assessed. Results: Exercise did not modify beta or alpha diversities regardless of the intensity (all P ≥ 0.062). The relative abundance of the Erysipelotrichaceae family (Bacillota phylum) (−0.3 ± 1.2 %; P = 0.031) was however reduced in the VIG-EX group. Coprococcus was the only genus showed a significant difference between MOD-EX and VIG-EX after the intervention, with its relative abundance increasing in MOD-EX (+0.4 ± 0.6 %; P = 0.005). None of these changes were related to the exercise-induced cardiometabolic benefits (all P ≥ 0.05). Conclusions: In young adults, a 24-week supervised concurrent exercise program, at moderate and vigorous intensities, resulted in minor changes in fecal microbiota composition, while neither alpha nor beta diversities were affected. Clinical trial registration: ClinicalTrials.gov ID: NCT02365129.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Endurance exercise; Gut; Microbiome; Resistance exercise; Succinate

Effects of Moderate Alcohol Consumption in Non-Alcoholic Fatty Liver Disease - Lemmer, Peter; Manka, Paul; Best, Jan; Kahraman, Alisan; Kälsch, Julia; Vilchez-vargas, Ramiro; Link, Alexander; Chiang, Hsin; Gerken, Guido; Canbay, Ali; Bechmann, Lars P.; Sydor, Svenja (Journal of Clinical Medicine, 2022)
Alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD) have emerged as leading causes of chronic liver diseases worldwide. ALD and NAFLD share several pathophysiological patterns as well as histological features, while clinically, they are distinguished by the amount of alcohol consumed daily. However, NAFLD coexists with moderate alcohol consumption in a growing proportion of the population. Here, we investigated the effects of moderate alcohol consumption on liver injury, lipid metabolism, and gut microbiota in 30 NAFLD-patients. We anonymously assessed drinking habits, applying the AUDIT- and CAGE-questionnaires and compared subgroups of abstainers vs. low to harmful alcohol consumers (AUDIT) and Cage 0–1 vs. Cage 2–4. Patients who did not drink any alcohol had lower levels of γGT, ALT, triglycerides, and total cholesterol. While the abundance of Bacteroidaceae, Bifidobacteriaceae, Streptococcaceae, and Ruminococcaceae was higher in the low to harmful alcohol drinking cohort, the abundance of Rikenellaceae was higher in the abstainers. Our study suggests that even moderate alcohol consumption has an impact on the liver and lipid metabolism, as well as on the composition of gut microbiota.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Lipid metabolism; Liver enzymes; Microbiota; Moderate alcohol consumption; NASH

EGF and BMPs Govern Differentiation and Patterning in Human Gastric Glands - Wölffling, Sarah; Daddi, Alice Anna; Imai-Matsushima, Aki; Fritsche, Kristin; Goosmann, Christian; Traulsen, Jan; Lisle, Richard; Schmid, Monika; Reines-Benassar, Maria del Mar; Pfannkuch, Lennart; Brinkmann, Volker; Bornschein, Jan; et al. (Gastroenterology, 2021)
Background & Aims: The homeostasis of the gastrointestinal epithelium relies on cell regeneration and differentiation into distinct lineages organized inside glands and crypts. Regeneration depends on Wnt/β-catenin pathway activation, but to understand homeostasis and its dysregulation in disease, we need to identify the signaling microenvironment governing cell differentiation. By using gastric glands as a model, we have identified the signals inducing differentiation of surface mucus-, zymogen-, and gastric acid–producing cells. Methods: We generated mucosoid cultures from the human stomach and exposed them to different growth factors to obtain cells with features of differentiated foveolar, chief, and parietal cells. We localized the source of the growth factors in the tissue of origin. Results: We show that epidermal growth factor is the major fate determinant distinguishing the surface and inner part of human gastric glands. In combination with bone morphogenetic factor/Noggin signals, epidermal growth factor controls the differentiation of foveolar cells vs parietal or chief cells. We also show that epidermal growth factor is likely to underlie alteration of the gastric mucosa in the precancerous condition atrophic gastritis. Conclusions: Use of our recently established mucosoid cultures in combination with analysis of the tissue of origin provided a robust strategy to understand differentiation and patterning of human tissue and allowed us to draw a new, detailed map of the signaling microenvironment in the human gastric glands.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Bone moprhogenetic protein; BMP Noggin; Differentiation; Epidermal growth factor; EGF; Epithelium; Mucosoids; patterning Gastric Cancer; Stomach

Endoscopic peroral jejunal fecal microbiota transplantation - Link, Alexander; Lachmund, Tim; Schulz, Christian; Weigt, Jochen; Malfertheiner, Peter (Digestive and Liver Disease, 2016)
Background Fecal microbiota transplantation (FMT) is a valuable treatment modality for recurrent Clostridium difficile (C. difficile) colitis. Multiple questions including the best delivery route and volume remain unanswered. Here, we report a case series of high-volume FMT using endoscopic jejunal application route. Methods In prospective observational study, FMT was performed using fresh specimen from healthy unrelated donors to the patients with recurrent or refractory C. difficile colitis. Selection of the route was based on the patient's preferences. Specimens of at least 50 g were dissolved in 500 ml of electrolyte solution and administered using endoscope directly in jejunum. Results All procedures led to cure of C. difficile colitis. With exception of one case the procedure was well tolerated. In two cases, we observed FMT-reflux into the stomach despite deep jejunal application and in single case the FMT-reflux led to tracheal aspiration and severe pneumonia. Conclusions High-volume FMT via endoscopic jejunal route is an effective treatment option that is well tolerated and easy to perform. Nevertheless, aspiration is potential life-threatening event that needs to be kept in mind during the FMT-procedure.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Application; Aspiration; Endoscopy; Fecal microbiota transplantation

Eosinophilic esophagitis: Comparison of clinical, endoscopic and histological scoring systems - Lorenz, Nikolas Johannes; Link, Alexander; Czapiewski, Piotr; Arnim, Ulrike Von (Zeitschrift für Gastroenterologie, 2022)
Background Eosinophilic Esophagitis (EoE) has received increasing attention as a disease entity, and it is now recognized as an important disorder of the Upper Gastrointestinal Tract. Topical corticosteroids (tCS) are effective in clinical-pathological remission induction (RI) and remission maintenance (RM) of active EoE. With scoring systems, such as clinical (SDI), endoscopic (EREFS), and histological (EoEHSS) systems, EoE can be graded, and its disease activity can be assessed. Objective To discover how closely results within each of the three scoring systems SDI, EREFS, and EoEHSS are correlated between initial diagnosis (ID), RI, and RM, and to determine how well scores from the three systems are intercorrelated at each time point. Methods Retrospective cohort analysis of patients with active EoE was performed between 2006 and 2020, with follow-up for up to 6 years. SDI, EREFS and EoEHSS scores were recorded at ID, at RI, and in RM. Evaluation employed descriptive statistics, the Friedman test, and Bonferroni-corrected post hoc pairwise comparisons. Results At RI 29 and at RM 19 EoE patients provided data. Significant correlations were found between EREFS and EoEHSS at RI and in RM. Pairwise comparisons showed significant differences between ID and RI for SDI, for EREFS, and for EoEHSS. Conclusion The scoring systems tested did not show intercorrelation at ID. Comparison revealed significant differences for SDI, EREFS, and EoEHSS between the systems at ID und RI, but not in RM, during tCS treatment. These results underline the efficacy of tCS (at RI and RM) in the treatment of active EoE.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Eosinophilic esophagitis; remission induction; remission maintenance; scoring systems

Epigenetic silencing of miR-137 is a frequent event in gastric carcinogenesis - Steponaitiene, Ruta; Kupcinskas, Juozas; Langner, Cosima; Balaguer, Francesc; Venclauskas, Linas; Pauzas, Henrikas; Tamelis, Algimantas; Skieceviciene, Jurgita; Kupcinskas, Limas; Malfertheiner, Peter; Link, Alexander (Molecular Carcinogenesis, 2016)
MicroRNAs (miRNA) are involved in posttranscriptional regulation of gene expression and are dysregulated during carcinogenesis. CpG island methylation of miR-137 is a common event in different cancers; however, the role of miR-137 in gastric cancer (GC) remains largely unexplored. In this study we aimed to characterize the epigenetic alterations of miR-137 in gastric carcinogenesis. We analyzed total 295 tissues including paired primary gastric cancer (T-GC) with corresponding adjacent gastric mucosa (N-GC), paired primary colorectal cancer (CRC) tissues with corresponding non-tumorous mucosa, gastric tissues from controls (N), and patients with chronic/atrophic gastritis (CG) with and without Helicobacter pylori infection. Bisulfite pyrosequencing and TaqMan RT-PCR were used to analyze miR-137 methylation and expression, respectively. Survival differences were evaluated using Kaplan-Meier analyses. miR-137 CpG island methylation was more frequent in tumorous compared to non-tumorous conditions and higher in CRC than in GC. In comparison to N-GC, miR 137 methylation level was lower in N and CG tissues, which correlates with Correas cascade. MiR-137 methylation inversely correlates with global LINE-1 methylation and miR-137 expression. miR-137 methylation was higher in intestinal type GC compared to diffuse one, and higher in antrum compared to cardia and corpus, however, miR-137 methylation was associated with worse prognosis in diffuse, but not in intestinal type of GC. The expression in colon was significantly higher compared to any gastric tissues suggesting functional difference. In summary, miR-137 methylation is a frequent event in gastrointestinal cancers which occurs early in stepwise manner during gastric carcinogenesis and inversely correlates with global methylation.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Colorectal cancer; Gastric cancer; Gastritis; Methylation; MicroRNA; MiR-137

Epigenetic silencing of miR-137 is an early event in colorectal carcinogenesis - Balaguer, Francesc; Link, Alexander; Lozano, Juan Jose; Cuatrecasas, Miriam; Nagasaka, Takeshi; Boland, C. Richard; Goel, Ajay (Cancer Research, 2010)
Global downregulation of microRNAs (miRNA) is a common feature in colorectal cancer (CRC). Whereas CpG island hypermethylation constitutes a mechanism for miRNA silencing, this field largely remains unexplored. Herein, we describe the epigenetic regulation of miR-137 and its contribution to colorectal carcinogenesis. We determined the methylation status of miR-137 CpG island in a panel of six CRC cell lines and 409 colorectal tissues [21 normal colonic mucosa from healthy individuals (N-N), 160 primary CRC tissues and their corresponding normal mucosa (N-C), and 68 adenomas]. TaqMan reverse transcription-PCR and in situ hybridization were used to analyze miR-137 expression. In vitro functional analysis of miR-137 was performed. Gene targets of miR-137 were identified using a combination of bioinformatic and transcriptomic approaches. We experimentally validated the miRNA:mRNA interactions. Methylation of the miR-137 CpG island was a cancer-specific event and was frequently observed in CRC cell lines (100%), adenomas (82.3%), and CRC (81.4%), but not in N-C (14.4%; P < 0.0001 for CRC) and N-N (4.7%; P < 0.0001 for CRC). Expression of miR-137 was restricted to the colonocytes in normal mucosa and inversely correlated with the level of methylation. Transfection of miR-137 precursor in CRC cells significantly inhibited cell proliferation. Gene expression profiling after miR-137 transfection discovered novel potential mRNA targets. We validated the interaction between miR-137 and LSD-1. Our data indicate that miR-137 acts as a tumor suppressor in the colon and is frequently silenced by promoter hypermethylation. Methylation silencing of miR-137 in colorectal adenomas suggests it to be an early event, which has prognostic and therapeutic implications. ©2010 AACR.
CRIS-Team Scopus Importer:2025-10-13

Erratum: Contrast-Enhanced Ultrasound Algorithms (CEUS-LIRADS/ESCULAP) for the Noninvasive Diagnosis of Hepatocellular Carcinoma-A Prospective Multicenter DEGUM Study (Ultraschall in Med (2020) DOI: 10.1055/a-1198-4874) - Schellhaas, Barbara; Bernatik, Thomas; Bohle, Wolfram; Borowitzka, Fanny; Chang, Johannes; Dietrich, Christoph F.; Dirks, Klaus; Donoval, Robert; Drube, Kristine; Friedrich-Rust, Mireen; Gall, Christine; Gittinger, Fleur; et al. (Ultraschall in der Medizin, 2020)
In the above article, the affiliations of two co-authors were indicated incorrectly. Correct: Albrecht Neesse, Golo Petzold Klinik für Gastroenterologie, gastrointestinale Onkologie und Endokrinologie, Universitätsmedizin Göttingen, Göttingen, Germany
CRIS-Team Scopus Importer:2020-11-20

European consensus conference on faecal microbiota transplantation in clinical practice - Cammarota, Giovanni; Ianiro, Gianluca; Tilg, Herbert; Rajilić-Stojanović, Mirjana; Kump, Patrizia; Satokari, Reetta; Sokol, Harry; Arkkila, Perttu; Pintus, Cristina; Hart, Ailsa; Segal, Jonathan; Aloi, Marina; et al. (Gut, 2017)
Faecal microbiota transplantation (FMT) is an important therapeutic option for Clostridium difficile infection. Promising findings suggest that FMT may play a role also in the management of other disorders associated with the alteration of gut microbiota. Although the health community is assessing FMT with renewed interest and patients are becoming more aware, there are technical and logistical issues in establishing such a non-standardised treatment into the clinical practice with safety and proper governance. In view of this, an evidence-based recommendation is needed to drive the practical implementation of FMT. In this European Consensus Conference, 28 experts from 10 countries collaborated, in separate working groups and through an evidence-based process, to provide statements on the following key issues: FMT indications; donor selection; preparation of faecal material; clinical management and faecal delivery and basic requirements for implementing an FMT centre. Statements developed by each working group were evaluated and voted by all members, first through an electronic Delphi process, and then in a plenary consensus conference. The recommendations were released according to best available evidence, in order to act as guidance for physicians who plan to implement FMT, aiming at supporting the broad availability of the procedure, discussing other issues relevant to FMT and promoting future clinical research in the area of gut microbiota manipulation. This consensus report strongly recommends the implementation of FMT centres for the treatment of C. difficile infection as well as traces the guidelines of technicality, regulatory, administrative and laboratory requirements.
CRIS-Team Scopus Importer:2025-10-13

Exploring microRNAs in Bile Duct Stents as Diagnostic Biomarkers for Biliary Pathologies - Hipler, Noam Mathias; Thon, Cosima; Lehr, Konrad; Furnari, Manuele; Obst, Wilfried; Keitel, Verena; Weigt, Jochen; Link, Alexander (Cancers, 2025)
Background/Objectives: Obstruction of the biliary duct may be caused by various conditions ranging from chronic inflammation to neoplasia, including cholangiocarcinoma (CCA). While the definite histological diagnosis of intrahepatic lesions is relatively straightforward, the diagnostic workup of biliary duct stenosis can be challenging, despite the availability of novel tools for intraductal diagnosis. This proof-of-principle study aimed to investigate whether microRNAs (miRNAs) from bile duct stents may be used as biomarkers to differentiate between various bile duct diseases. Methods: For this purpose, we included 100 patients with one or more bile duct stents for various reasons, including malignant disease (n = 40), stenosis due to liver transplantation or surgery (n = 60), and cholangitis (n = 42). During endoscopic retrograde cholangiography, the stents were collected, and miRNA analyses were performed to evaluate miR-16, miR-21, and miR-223. Results: All studied miRNAs were successfully detected from the specimens obtained from the bile duct stents and were comparable in different stents from the same subjects. Following normalization, significant increases in miR-16, -21, and -223 levels were identified in patients with cholangitis compared to specimens from a non-inflammatory cohort. However, when comparing the data from patients in the malignant and non-malignant cohorts, the individual levels of miR-16, miR-21, and miR-223 showed high variation, without reaching a statistically significant difference. Conclusions: In summary, bile duct stents can be considered as potential sources of intraductal biomarkers, specifically miRNAs. Further profiling and validation analyses are necessary to identify the most appropriate miRNA targets for differentiating bile duct diseases.
CRIS-Team Scopus Importer:2025-10-13
Keywords: bile ducts; cholangiocarcinoma; cholangitis; cholestasis; miRNA; stents

Expression of aurora kinase A correlates with the Wnt-modulator RACGAP1 in gastric cancer - Bornschein, Jan; Nielitz, Jessica; Drozdov, Ignat; Selgrad, Michael; Wex, Thomas; Jechorek, Doerthe; Link, Alexander; Vieth, Michael; Malfertheiner, Peter (Cancer Medicine, 2016)
Canonical Wnt signaling is involved in gastric carcinogenesis. The aim of this study was to identify the link between Wnt signaling and aurora kinase A (AURKA), a target for the treatment of gastrointestinal cancers. Publicly available microarray data were used to identify phenotype-specific protein-protein interaction (PPI) subnetworks. The in silico analysis revealed a gastric cancer-specific PPI subnetwork consisting of 2745 proteins and 50,935 interactions. We focused on the link of AURKA to a Wnt-specific interaction module consisting of 92 proteins. There was a direct association of AURKA with Rac GTPase-activating protein 1 (RACGAP1), as well as with CTNBB1 (β-catenin) and CDKN1A as second-order interactors. Differential expression analysis revealed a significant downregulation of both AURKA and RACGAP1 in gastric cancer compared to noncancer controls. Biopsies from a prospective cohort of 56 patients with gastric cancer (32 intestinal type, 24 diffuse type) and 20 noncancer controls were used for validation of the identified targets. The RT-PCR data confirmed a strong correlation of AURKA and RACGAP1 gene expression both in the tumor, the tumor-adjacent and the tumor-distant mucosa. RACGAP1 in the tumor was also associated with CTNBB1 expression, and inversely associated with CDKN1A gene expression. Immunohistochemistry confirmed expression of the RACGAP1 protein in gastric cancer and the tumor-adjacent mucosa. RACGAP1 expression was not associated with tumor stage, grading, Lauren type, Helicobacter pylori infection, or age. In conclusion, AURKA is directly associated with the expression of RACGAP1, a modulator of the canonical Wnt signaling pathway.
CRIS-Team Scopus Importer:2025-03-05
Keywords: AURKA; CDKN1A; Gastric cancer; RACGAP1; Wnt

Expression of microRNAs in the ascites of patients with peritoneal carcinomatosis and peritonitis - Schindler, Philipp; Kupcinskas, Juozas; Juzenas, Simonas; Skieceviciene, Jurgita; Salteniene, Violeta; Schulz, Christian; Weigt, Jochen; Malfertheiner, Peter; Link, Alexander (Cancer, 2018)
BACKGROUND: Peritoneal carcinomatosis (PCA) has a prognostic role in patients with gastrointestinal cancers. The differential diagnosis may be challenging due to the low sensitivity of cytology. Although microRNAs (miRNAs) have been a focus of various specimens and diseases, to the best of the authors' knowledge only limited knowledge exists regarding ascites. Herein, the authors systematically evaluated preanalytical factors and the potential of miRNAs as biomarkers of ascites. METHODS: The authors prospectively analyzed samples from patients with PCA, spontaneous bacterial peritonitis (SBP), and portal hypertension (no SBP/PCA). Various preanalytical factors such as extraction kits, sample storage, stability, and processing were systematically evaluated. MiRNA expression profiling using TaqMan Low Density Array and quantitative reverse transcriptase-polymerase chain reaction were used to evaluate miRNA expression. RESULTS: All selected miRNAs were found to be reliably detectable in ascites samples. Ascites miRNAs were well preserved from degradation with required short-term and long-term stability. MiRNA expression profiling in patients with PCA compared with those with no SBP/PCA revealed miR-21, miR-186, miR-222, and miR-483-5p to be upregulated and miR-26b to be downregulated. MiRNA expression validation analysis confirmed higher expression levels of miR-21 and miR-186 in patients with PCA compared with those with no SBP/PCA, whereas miR-223 was significantly upregulated in patients with SBP. A simple proportion score between miR-21 and miR-223 allowed the authors to discriminate between the patients with PCA and those with SBP with an area under the curve of 0.982 (95% confidence interval, 0.943-1.022). CONCLUSIONS: The data from the current study provide novel evidence of the differential expression of miRNAs in ascites from patients with PCA and SBP, which may offer an additional miRNA-based molecular approach for the differential diagnosis of PCA. Cancer Cytopathol 2018;126:353-63. © 2018 American Cancer Society.
CRIS-Team Scopus Importer:2025-10-13
Keywords: ascites; microRNA; peritoneal carcinomatosis; peritonitis

Factors Affecting Performance of DNA Methylation as a Potential Biomarker in Ascites for Peritonitis and Peritoneal Carcinomatosis - Bose, Katrin; Scurt, Florian G.; Thon, Cosima; Franke, Sabine; Schulz, Christian; Malfertheiner, Peter; Link, Alexander (Journal of Gastrointestinal and Liver Diseases, 2023)
Background & Aims: Despite limited sensitivity, the gold standard for the diagnosis of malignant cells in ascites is still cytology. The aim of this prospective proof-of-principle study was to evaluate DNA methylation as a molecular tool for the differential diagnosis of benign and malignant ascites. Methods: A cohort of 79 patients with malignant and non-malignant ascites was prospectively enrolled. Ascites was assessed by cytopathological and laboratory examination. Cell pellets obtained by centrifugation were analyzed for differences in DNA methylation of of long interspersed nuclear element-1 (LINE-1) and microRNA-137. Quantitative determination of methylation in bisulfite-converted DNA was performed by pyrosequencing. In a subsequent stage, we compared our data to previously published data in the field following systematic review of the literature. Results: Methylation status of studied LINE-1 and microRNA-137 could be reliably detected in all samples. Systematic evaluation revealed reliable reproducibility with satisfactory short-and long-term stability against degradation. Ascites from patients with a malignancy had a significantly higher methylation level of microRNA-137 compared with patients without tumor disease, whereas patients with peritonitis had significantly decreased methylation of microRNA-137. In contrast, differences in the measurement of the methylation status of LINE-1 could only be detected between patients with portal hypertension and a combination of malignant and infectious ascites. Inflammatory cells reflecting peritonitis correlated to DNA methylation changes. Conclusions: Analysis of DNA methylation in ascites is technically feasible, well reproducible and may lead to identification of potential biomarkers for peritoneal carcinomatosis and other conditions. Inflammatory cells due to peritonitis may also be associated with DNA methylation changes and need to be considered in future studies. Profiling studied under standardized conditions will be needed to identify the appropriate biomarkers for differential diagnosis of ascites.
CRIS-Team Scopus Importer:2025-10-13
Keywords: DNA methylation; LINE-1; microRNA-137-ascites; miR-137; peritoneal carcinomatosis; peritonitis

Feasibility of combined screening for upper gastrointestinal adenocarcinoma risk by serology and Cytosponge testing: The SUGAR study - Xu, Yiwang; Miremadi, Ahmad; Link, Alexander; Malfertheiner, Peter; Fitzgerald, Rebecca C.; Bornschein, Jan (Journal of Clinical Pathology, 2019)
Aims Aim was to assess the feasibility of serum markers to identify individuals at risk for gastro-oesophageal adenocarcinoma to reduce the number of individuals requiring invasive assessment by endoscopy. Methods Blood samples from 56 patients with Barrett's oesophagus and 202 non-Barrett controls who previously took part in a trial assessing the accuracy of the Cytosponge for Barrett's oesophagus were assessed for serum pepsinogen (PG) 1 and 2, gastrin-17, trefoil factor 3 (TFF3) and Helicobacter pylori infection. Results PG1 was pathological (<50 ng/mL) in 26 patients (10.1%), none of whom had Barrett's oesophagus (p<0.001). Smoking and drinking had no influence on these results. Pathological PG1 was associated with stomach pain (p=0.029), disruption of sleep (p=0.027) and disruption of diet by symptoms (p=0.019). Serum TFF3 was not associated with any clinical parameter. Conclusions Assessment of serum PG1 could be combined with a test for Barrett's oesophagus to identify additional patients requiring endoscopy.
CRIS-Team Scopus Importer:2025-10-13
Keywords: barrett's oesophagus; gastric atrophy; gastric cancer; pepsinogens; TFF3

Feasibility of fecal microRNAs as novel biomarkers for pancreatic cancer - Link, Alexander; Becker, Verena; Goel, Ajay; Wex, Thomas; Malfertheiner, Peter (PLoS ONE, 2012)
Introduction: Pancreatic cancer (PCA) is an aggressive tumor that associates with high mortality rates. Majority of PCA patients are diagnosed usually at late tumor stages when the therapeutic options are limited. MicroRNAs (miRNA) are involved in tumor development and are commonly dysregulated in PCA. As a proof-of-principle study, we aimed to evaluate the potential of fecal miRNAs as biomarkers for pancreatic cancer. Materials and Methods: Total RNA was extracted from feces using Qiagen's miRNA Mini Kit. For miRNA expression analyses we selected a subset of 7 miRNAs that are frequently dysregulated in PCA (miR-21, -143, -155, -196a, -210, -216a, -375). Subsequently, expression levels of these miRNAs were determined in fecal samples from controls (n = 15), chronic pancreatitis (n = 15) and PCA patients (n = 15) using quantitative TaqMan-PCR assays. Results: All selected miRNAs were detectable in fecal samples with high reproducibility. Four of seven miRNAs (miR-216a, -196a, -143 und -155) were detected at lower concentrations in feces of PCA patients when compared to controls (p<0.05). Analysis of fecal miRNA expression in controls and patients with chronic pancreatitis and PCA revealed that the expression of miR-216a, -196a, -143 und -155 were highest in controls and lowest in PCA. The expression of the remaining three miRNAs (miR-21, -210 and -375) remained unchanged among controls and the patients with either chronic pancreatitis or PCA. Conclusion: Our data provide novel evidence for the differential expression of miRNAs in feces of patients with PCA. If successfully validated in large-scale prospective studies, the fecal miRNA biomarkers may offer novel tools for PCA screening research. © 2012 Link et al.
CRIS-Team Scopus Importer:2025-10-13

Fecal Microbiota Transfer (FMT) in Germany - Status and Perspective Fäkaler Mikrobiota-Transfer (FMT) in Deutschland - Status und Perspektive - Stallmach, Andreas; Von Müller, Lutz; Storr, Martin; Link, Alexander; Konturek, Peter C.; Solbach, Philipp Christoph; Weiss, Karl Heinz; Wahler, Steffen; Vehreschild, Maria J.G.T. (Zeitschrift für Gastroenterologie, 2022)
Introduction Fecal microbiota transfer (FMT) is a treatment to modulate the gastrointestinal microbiota. Its use in recurrent Clostridioides difficile infection (rCDI) is established throughout Europe and recommended in national and international guidelines. In Germany, the FMT is codeable in the hospital reimbursement system. A comprehensive survey on the frequency of use based on this coding is missing so far. Material and methodology Reports of the Institute for Hospital Remuneration (InEK), the Federal Statistical Office (DESTATIS), and hospital quality reports 2015-2021 were examined for FMT coding and evaluated in a structured expert consultation. Results Between 2015 and 2021, 1,645 FMT procedures were coded by 175 hospitals. From 2016 to 2018, this was a median of 293 (274-313) FMT annually, followed by a steady decline in subsequent years to 119 FMT in 2021. Patients with FMT were 57.7% female, median age 74 years, and FMT was applied colonoscopically in 72.2%. CDI was the primary diagnosis in 86.8% of cases, followed by ulcerative colitis in 7.6%. Discussion In Germany, FMT is used less frequently than in the European comparison. One application hurdle is the regulatory classification of FMT as a non-approved drug, which leads to significantly higher costs in manufacturing and administration and makes reimbursement difficult. The European Commission recently proposed a regulation to classify FMT as a transplant. This could prospectively change the regulatory situation of FMT in Germany and thus contribute to a nationwide offer of a therapeutic procedure recommended in guidelines.
CRIS-Team Scopus Importer:2025-10-13
Keywords: clostridioides difficile; fecal microbiota transfer; hospital data

Fecal microRNAs as novel biomarkers for colon cancer screening - Link, Alexander; Balaguer, Francesc; Shen, Yan; Nagasaka, Takeshi; Lozano, Juan José; Boland, C. Richard; Goel, Ajay (Cancer Epidemiology Biomarkers & Prevention, 2010)
Introduction: Colorectal cancer (CRC) is the second leading cause of cancer-related deaths, but currently available noninvasive screening programs have achieved only a modest decrease in mortality. MicroRNAs (miRNA) play an important role in a wide array of biological processes and are commonly dysregulated in neoplasia. We aimed to evaluate the feasibility of fecal miRNAs as biomarkers for colorectal neoplasia screening. Materials and Methods: Total RNA was extracted from freshly collected stool samples from 8 healthy volunteers and 29 samples collected via fecal occult blood testing from subjects with normal colonoscopies, colon adenomas, and CRCs. miRNA expression analyses were done with TaqMan quantitative reverse transcription-PCR for a subset of miRNAs. Illumina miRNA microarray profiling was done to evaluate the differences in expression patterns between normal colonic mucosa tissues and stool samples from healthy subjects. Results: We efficiently extracted miRNAs from stool specimens using our developed protocol. Data from independent experiments showed high reproducibility for miRNA extraction and expression. miRNA expression patterns were similar in stool specimens among healthy volunteers, and reproducible in stool samples that were collected serially in time from the same individuals. miRNA expression profiles from 29 patients showed higher expression of miR-21 and miR-106a in patients with adenomas and CRCs compared with individuals free of colorectal neoplasia. Conclusion: Our data indicate that miRNAs could be extracted from stool easily and reproducibly. The stools of patients with colorectal neoplasms have unique and identifiable patterns of miRNA expression. Impact: Fecal miRNAs may be an excellent candidate for the development of a noninvasive screening test for colorectal neoplasms. ©2010 AACR.
CRIS-Team Scopus Importer:2025-10-13

First Case of Covid-19 in the United States - Link, Alexander; Hold, Georgina (New England Journal of Medicine, 2020)
CRIS-Team Scopus Importer:2025-10-13

Food-Derived Xeno-microRNAs: Influence of Diet and Detectability in Gastrointestinal Tract—Proof-of-Principle Study - Link, Jastin; Thon, Cosima; Schanze, Denny; Steponaitiene, Ruta; Kupcinskas, Juozas; Zenker, Martin; Canbay, Ali; Malfertheiner, Peter; Link, Alexander (Molecular Nutrition & Food Research, 2019)
Scope: Diet is amongst the most crucial factors contributing to the multistep process of carcinogenesis. The role of exogenous microRNAs (miRNAs) is still debatable. In this proof-of-principle work, the presence of miRNAs in a variety of foods, its stability to processing, and detectability in GI mucosa and feces are studied and the effect of short-term diet on human- or plant-derived miRNAs in feces and blood is examined. Methods and results: Animal and plant miRNAs are detected in all foods irrespective of processing. Animal-derived foods showed the highest miRNA level and the lowest is found in cheese and milk. The impact of the short-term vegetarian or meat-rich diet on blood and feces miRNA is evaluated in healthy subjects using qPCR and Affymetrix profiling. Diet is not associated with changes in ultraconserved miRNAs. However, a vegetarian diet is associated with an increase of miR-168 in feces but not in blood. Overall, plant miR-168 is detectable in normal GI mucosa and in colorectal cancer. Conclusions: Food provides a great source of miRNAs and diet may be associated with changes in xenomiRs. Plant-derived miR-168 is ubiquitously present in feces, normal mucosa, and cancer. Further studies are needed to evaluate the functional interaction between diet-derived miRNAs and GI tract.
CRIS-Team Scopus Importer:2025-10-13
Keywords: diet; feces; food; microRNA; xenomiRs

Fusobacterium nucleatum is associated with worse prognosis in Lauren’s diffuse type gastric cancer patients - Boehm, Ellen Teresa; Thon, Cosima; Kupcinskas, Juozas; Steponaitiene, Ruta; Skieceviciene, Jurgita; Canbay, Ali; Malfertheiner, Peter; Link, Alexander (Scientific Reports, 2020)
Fusobacterium nucleatum (F. nucleatum) is frequently detected in primary colorectal cancer (CRC) and matching metastasis, and has been linked to a worse prognosis. We investigated the presence of F. nucleatum in gastric cancer (GC) and gastric preneoplastic conditions of the stomach, and its potential prognostic value in GC patients. Fusobacterium spp. and F. nucleatum were quantified in various specimens from gastrointestinal tract including paired CRC and GC tissues using probe-based qPCR. Fusobacterium spp. and F. nucleatum were more frequently found in tumorous tissue of CRC and GC compared to non-tumorous tissues. The frequency and bacterial load were higher in CRC compared to GC patients. F. nucleatum positivity showed no association to chronic gastritis or preneoplastic conditions such as intestinal metaplasia. F. nucleatum-positivity was associated with significantly worse overall survival in patients with Lauren’s diffuse type, but not with intestinal type GC. There was no association with gender, Helicobacter pylori-status, tumor stage or tumor localization. However, F. nucleatum was positively associated with patient’s age and a trend for a lower global long interspersed element-1 DNA methylation. In conclusion, our work provides novel evidence for clinical relevance of F. nucleatum in GC by showing an association between F. nucleatum positivity with worse prognosis of patients with Laurens’s diffuse type gastric cancer. Further studies are necessary to explore related mechanistic insights and potential therapeutic benefit of targeted antibiotic treatment in GC patients.
CRIS-Team Scopus Importer:2025-10-13

Fusobacterium nucleatum: Unraveling its potential role in gastric carcinogenesis - Petkevicius, Vytenis; Lehr, Konrad; Kupcinskas, Juozas; Link, Alexander (World Journal of Gastroenterology, 2024)
Fusobacterium nucleatum (F. nucleatum) is a Gram-negative anaerobic bacterium that plays a key role in the development of oral inflammation, such as periodontitis and gingivitis. In the last 10 years, F. nucleatum has been identified as a prevalent bacterium associated with colorectal adenocarcinoma and has also been linked to cancer progression, metastasis and poor disease outcome. While the role of F. nucleatum in colon carcinogenesis has been intensively studied, its role in gastric carcinogenesis is still poorly understood. Although Helicobacter pylori infection has histo-rically been recognized as the strongest risk factor for the development of gastric cancer (GC), with recent advances in DNA sequencing technology, other members of the gastric microbial community, and F. nucleatum in particular, have received increasing attention. In this review, we summarize the existing knowledge on the involvement of F. nucleatum in gastric carcinogenesis and address the potential translational and clinical significance of F. nucleatum in GC.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Fusobacterium nucleatum; Gastric cancer; Gastric microbiota; Preneoplastic changes; Prognosis

Gastric cancer – clinical and epidemiological aspects - Venerito, Marino; Link, Alexander; Rokkas, Theodoros; Malfertheiner, Peter (Helicobacter, 2016)
Gastric cancer (GC) ranks fifth for cancer incidence and second for cancer deaths. Epidemiological data showed that survivors of Hodgkin's lymphoma and patients with pernicious anemia etiologically linked to autoimmune gastritis are at increased risk of GC. Screening of patients with autoimmune thyroid disease by means of pepsinogen (PG) I and PG I/II detected autoimmune gastritis with oxyntic gastric atrophy in one of four patients and may be recommended for GC prevention purposes. The International Agency for Research on Cancer reported a positive association between consumption of processed meet and increased GC risk. A new GC risk prediction model based on biological markers, age, gender, smoking status, family history of GC, and consumption of highly salted food showed good predictive performance, and might prompt individuals to modify their lifestyle habits, attend regular check-up visits or participate in screening programs. A novel GC classification based on gene expression of primary resected cancers correlated with clinicopathological features. Noncoding RNA for GC screening remains the focus of multiple studies. Patients with early GC undergoing endoscopic resection are more likely to develop metachronous lesions than patients undergoing surgery and endoscopic surveillance is warranted in this special cohort. The addition of gastrectomy to chemotherapy did not improve survival of patients with advanced GC and a single noncurable factor. Apatinib, a novel oral vascular endothelial growth factor receptor 2 tyrosine kinase inhibitor, improved the median overall survival of patients with advanced GC and progressive disease after two or more lines of prior chemotherapy of nearly 3 months.
CRIS-Team Scopus Importer:2025-10-13
Keywords: epidemiology; gastric cancer; prevention; therapy

Gastric Epithelial Expression of IL-12 Cytokine Family in Helicobacter pylori Infection in Human: Is it Head or Tail of the Coin? - Al-Sammak, Fadi; Kalinski, Thomas; Weinert, Sönke; Link, Alexander; Wex, Thomas; Malfertheiner, Peter (PLoS ONE, 2013)
Recently, there has been a growing interest in an expanding group of cytokines known as "IL-12 family". The so far gained knowledge about these cytokines, as crucial playmakers in mucosal immunity, has not yet been sufficiently investigated in the context of Helicobacter pylori infection. All genes encoding the monomeric components of these cytokines and their corresponding receptors were examined in gastric epithelial cell lines (AGS and MKN-28) after being infected with 4 H. pylori strains: BCM-300, P1 wild-type, and P1-derived isogenic mutants lacking cytotoxin-associated gene A (cagA) or virulence gene virB7 (multiplicity of infection=50). Both infected and uninfected samples were analyzed after 24h and 48h using real-time quantitative polymerase chain reaction (RT-qPCR). Gene expression analysis demonstrated a strong upregulation of IL23A (encodes p19) by infection, whereas IL23R, Epstein-Barr virus-induced gene 3 (EBI3), IL6ST, IL12A, and IL27RA were found to be expressed, but not regulated, or to a lesser extent. Transcripts of IL12RB2, IL12B, IL12RB1, and IL27A were not detected. Interestingly, P1 resulted in stronger alterations of expression than CagA mutant and BCM-300, particularly for IL23A (59.7-fold versus 32.4- and 6.7-fold, respectively in AGS after 48h, P<.05), whereas no changes were seen with VirB7 mutant. In a proof-of-principle experiment, we demonstrated epithelial-derived expression of IL-12, p19, and Ebi3 in gastric mucosa of gastritis patients using immunohistochemistry (IHC). Unlike IL-12 and Ebi3, increased immunostaining of p19 was observed in H. pylori gastritis. Herein, we highlight the potential role of gastric epithelial cells in mucosal immunity, not only because they are predominant cell type in mucosa and initial site of host-bacterial interaction, but also as a major contributor to molecules that are thought to be primarily expressed by immune cells so far. Of these molecules, p19 was the most relevant one to H. pylori infection in terms of expression and localization. © 2013 Al-Sammak et al.
CRIS-Team Scopus Importer:2025-10-13

Gene polymorphisms of micrornas in helicobacter pylori-induced high risk atrophic gastritis and gastric cancer - Kupcinskas, Juozas; Wex, Thomas; Link, Alexander; Leja, Marcis; Bruzaite, Indre; Steponaitiene, Ruta; Juzenas, Simonas; Gyvyte, Ugne; Ivanauskas, Audrius; Ancans, Guntis; Petrenkiene, Vitalija; Skieceviciene, Jurgita; et al. (PLoS ONE, 2014)
Background and aims: MicroRNAs (miRNAs) are known for their function as translational regulators of tumor suppressor or oncogenes. Single nucleotide polymorphisms (SNPs) in miRNAs related genes have been shown to affect the regulatory capacity of miRNAs and were linked with gastric cancer (GC) and premalignant gastric conditions. The purpose of this study was to evaluate potential associations between miRNA-related gene polymorphisms (miR-27a, miR-146a, miR-196a-2, miR-492 and miR-608) and the presence of GC or high risk atrophic gastritis (HRAG) in European population. Methods: Gene polymorphisms were analyzed in 995 subjects (controls: n = 351; GC: n = 363; HRAG: n = 281) of European descent. MiR-27a T>C (rs895819), miR-146a G>C (rs2910164), miR-196a-2 C>T (rs11614913), miR-492 G>C (rs2289030) and miR-608 C>G (rs4919510) SNPs were genotyped by RT-PCR. Results: Overall, SNPs of miRNAs were not associated with the presence of GC or HRAG. We observed a tendency for miR-196a-2 CT genotype to be associated with higher risk of GC when compared to CC genotype, however, the difference did not reach the adjusted P-value (odds ratio (OR) - 1.46, 95% confidence interval (CI) 1.03-2.07, P = 0.032). MiR-608 GG genotype was more frequent in GC when compared to controls (OR -2.34, 95% CI 1.08-5.04), but significance remained marginal (P = 0.029). A similar tendency was observed in a recessive model for miR-608, where CC + CG vs GG genotype comparison showed a tendency for increased risk of GC with OR of 2.44 (95% CI 1.14-5.22, P = 0.021). The genotypes and alleles of miR-27a, miR-146a, miR-196a-2, miR-492 and miR-608 SNPs had similar distribution between histological subtypes of GC and were not linked with the presence of diffuse or intestinal-type GC. Conclusions: Gene polymorphisms of miR-27a, miR-146a, miR-196a-2, miR-492, miR-492a and miR-608 were not associated with the presence of HRAG, GC or different histological subtypes of GC in European subjects. © 2014 Kupcinskas et al.
CRIS-Team Scopus Importer:2025-10-13

Genetic mechanisms for Se(VI) reduction and synthesis of trigonal 1-D nanostructures in Stenotrophomonas bentonitica: Perspectives in eco-friendly nanomaterial production and bioremediation - Pinel-Cabello, María; Jauregui, Ruy; Jroundi, Fadwa; Geffers, Robert; Jarek, Michael; Link, Alexander; Vilchez-Vargas, Ramiro; Merroun, Mohamed L. (Science of the Total Environment, 2023)
Selenate (Se(VI)) is one of the most soluble and toxic species of Se. Microbial Se(VI) reduction is an efficient tool for bioremediation strategies. However, this process is limited to a few microorganisms, and its molecular basis remains unknown. We present detailed Se(VI)-resistance mechanisms under 50 and 200 mM, in Stenotrophomonas bentonitica BII-R7, coupling enzymatic reduction of Se(VI) to formation of less toxic trigonal Se (t-Se). The results reveal a concentration-dependent response. Despite the lack of evidence of Se(VI)-reduction to Se(0) under 50 mM Se(VI), many genes were highly induced, indicating that Se(VI)-resistance could be based on intracellular reduction to Se(IV), mainly through molybdenum-dependent enzymes (e.g. respiratory nitrate reductase), and antioxidant activity by enzymes like glutathione peroxidase. Although exposure to 200 mM provoked a sharp drop in gene expression, a time-dependent process of reduction and formation of amorphous (a), monoclinic (m) and t-Se nanostructures was unravelled: a-Se nanospheres were initially synthesized intracellularly, which would transform into m-Se and finally into t-Se nanostructures during the following phases. This is the first work describing an intracellular Se(VI) reduction and biotransformation process to long-term stable and insoluble t-Se nanomaterials. These results expand the fundamental understanding of Se biogeochemical cycling, and the effectiveness of BII-R7 for bioremediation purposes.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Bioremediation; Microscopy; Selenium; Stenotrophomonas; Transcriptomics

Genetic variation in TERT modifies the risk of hepatocellular carcinoma in alcohol-related cirrhosis: Results from a genome-wide case-control study - Buch, Stephan; Innes, Hamish; Lutz, Philipp Ludwig; Nischalke, Hans Dieter; Marquardt, Jens U.; Fischer, Janett; Weiss, Karl Heinz; Rosendahl, Jonas; Marot, Astrid; Krawczyk, Marcin; Casper, Markus; Lammert, Frank; et al. (Gut, 2023)
Objective Hepatocellular carcinoma (HCC) often develops in patients with alcohol-related cirrhosis at an annual risk of up to 2.5%. Some host genetic risk factors have been identified but do not account for the majority of the variance in occurrence. This study aimed to identify novel susceptibility loci for the development of HCC in people with alcohol related cirrhosis. Design Patients with alcohol-related cirrhosis and HCC (cases: n=1214) and controls without HCC (n=1866), recruited from Germany, Austria, Switzerland, Italy and the UK, were included in a two-stage genome-wide association study using a case-control design. A validation cohort of 1520 people misusing alcohol but with no evidence of liver disease was included to control for possible association effects with alcohol misuse. Genotyping was performed using the InfiniumGlobal Screening Array (V.24v2, Illumina) and the OmniExpress Array (V.24v1-0a, Illumina). Results Associations with variants rs738409 in PNPLA3 and rs58542926 in TM6SF2 previously associated with an increased risk of HCC in patients with alcohol-related cirrhosis were confirmed at genome-wide significance. A novel locus rs2242652(A) in TERT (telomerase reverse transcriptase) was also associated with a decreased risk of HCC, in the combined meta-analysis, at genome-wide significance (p=6.41×10 -9, OR=0.61 (95% CI 0.52 to 0.70). This protective association remained significant after correction for sex, age, body mass index and type 2 diabetes (p=7.94×10 -5, OR=0.63 (95% CI 0.50 to 0.79). Carriage of rs2242652(A) in TERT was associated with an increased leucocyte telomere length (p=2.12×10 -44). Conclusion This study identifies rs2242652 in TERT as a novel protective factor for HCC in patients with alcohol-related cirrhosis.
CRIS-Team Scopus Importer:2025-10-13
Keywords: genetic polymorphisms; hepatocellular carcinoma

Granular biomass technology for providing drinking water: microbial versatility and nitrate performance in response to carbon source - Muñoz-Palazon, Barbara; Rodriguez-Sanchez, Alejandro; Gonzalez-Lopez, Jesus; Rosa-Masegosa, Aurora; Gorrasi, Susana; Vilchez-Vargas, Ramiro; Link, Alexander; Gonzalez-Martinez, Alejandro (Applied Water Science, 2023)
The aerobic granular biomass technology was optimized for treating nitrate-polluted groundwater based on the biological denitrification processes in order to provide drinking water. Reactors inoculated with granular biomass were operated at progressively lower C/N rate using acetate and methanol to encourage heterotrophic denitrification, in order to meet the recommended requirements described by European Drinking Water Framework Directive. The granulation and long-term stability of granular biomass under low C/N were successful for all stages, demonstrated compactness of granules and absence of filamentous microorganisms. The nitrate removal was similar in methanol- and acetate-fed reactors, occurring in both cases nitrate removal ratios > 80%, and fact allows the selection of one of both depending groundwater polluted case. Also, feeding reactors with 2 C/N ratio showed nitrate removal values of ≥ 95%, treating highly polluted groundwater (100 mg·L−1). The microbial diversity was higher in the methanol-fed reactor with representative phylotypes as Flavobacterium, Cytophagaceae, NS9 marine group, while species richness was higher in the acetate-fed reactor, which was mainly represented by Flavobacterium genus. Statistical analyses revealed the higher resilience of bacterial population on granules fed with acetate, showing more resistance under drop C/N ratio. Oscillating pollution in groundwater during seasonal periods should be treated using acetate as carbon source for denitrification carried out by granular biomass, while stable pollution concentrations over time allow the use of methanol as a carbon source since the greater microbial diversity allows the elimination of other contaminants present in groundwater.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Aerobic granular technology; Bacterial community; Carbon source; Groundwater pollution; Nitrate-polluted; Real time PCR

Gut microbial similarity in twins is driven by shared environment and aging - Vilchez-Vargas, Ramiro; Skieceviciene, Jurgita; Lehr, Konrad; Varkalaite, Greta; Thon, Cosima; Urba, Mindaugas; Morkūnas, Egidijus; Kucinskas, Laimutis; Bauraite, Karolina; Schanze, Denny; Zenker, Martin; Malfertheiner, Peter; et al. (EBioMedicine, 2022)
Background: Human gut microbiome composition is influenced by genetics, diet and environmental factors. We investigated the microbial composition in several gastrointestinal (GI) compartments to evaluate the impact of genetics, delivery mode, diet, household sharing and aging on microbial similarity in monozygotic and dizygotic twins. Methods: Fecal, biopsy and saliva samples were obtained from total 108 twins. DNA and/or RNA was extracted and the region V1-V2 of the 16S rRNA gene was amplified and sequenced. Bray-Curtis similarity was used for further microbiome comparisons, Mann-Whitney test was applied to evaluate the significant differences between groups and Spearman test was applied to reveal potential correlations between data. Findings: The global bacterial profiles were grouped into two clusters separating the upper and lower GI. The upper GI microbiome composition was strictly dependent on the Helicobacter pylori status. With a positivity rate of 55%, H. pylori completely colonized the stomach and separated infected twins from non-infected twins irrespective of zygosity status. Lower GI microbiome similarity between the twins was defined mainly by household-sharing and aging; whereas delivery mode and host genetics had no influence. There was a progredient decrease in the bacterial similarity with aging. Shared vs. non-shared phylotypes analysis showed that in both siblings the shared phylotypes progressively diminished with aging, while the non-shared phylotypes increased. Interpretation: Our findings strongly highlight the aging and shared household as they key determinants in gut microbial similarity and drift in twins irrespective of their zygotic state. Funding: This work was supported by the grant of the Research Council of Lithuania (Project no. APP-2/2016) and also partially supported by the funds of European Commission through the “European funds for regional development” (EFRE) as well as by the regional Ministry of Economy, Science and Digitalization as part of the “LiLife” Project as part of the “Autonomy in old Age” research group (Project ID: ZS/2018/11/95324).
CRIS-Team Scopus Importer:2025-10-13
Keywords: 16S rRNA sequencing; Aging; Equality; Helicobacter pylori; Microbiome; Shared household; Stomach

Helicobacter pylori eradication therapy is not associated with the onset of inflammatory bowel diseases. A case-control study - Rosania, Rosa; Arnim, Ulrike Von; Link, Alexander; Rajilic-Stojanovic, Mirjana; Franck, Caspar; Canbay, Ali; Malfertheiner, Peter; Venerito, Marino (Journal of Gastrointestinal and Liver Diseases, 2018)
Background & Aims: A negative association between H. pylori and inflammatory bowel disease (IBD) has been previously reported. There were also case reports suggesting a new onset of IBD 6-12 months after H. pylori eradication therapy. In a case-control study we investigated whether previous H. pylori eradication therapy was associated with the risk of developing IBD. Methods: IBD outpatients with both Crohn´s disease (CD) and ulcerative colitis (UC) were enrolled. Age-and sex-matched blood donors served as controls in a 1:2 fashion. Information on demographics, medical history, previous H. pylori infection and eradication therapy was recorded. Serum samples for H. pylori serology testing (anti-H. pylori-IgG and anti-CagA-IgG) were obtained. Controls that received H. pylori eradication therapy during the 12 months previous to enrollment were excluded. Results: Overall, 127 IBD patients (CD N= 90; UC N= 37) and 254 controls were enrolled. The prevalence of H. pylori infection (positive H. pylori serology and/or previous eradication) in IBD patients and controls was 11% and 23%, respectively (OR 0.4, 95% CI 0.21-0.74, p<0.003). Four patients (3%) developed IBD (3 MC and 1 CU) after receiving successful H. pylori eradication (latency 6-12 months). The rate of previous H. pylori eradication therapy in patents who successively developed IBD was lower but not statistically different from that observed in the control group (OR 0.43, 95% CI 0.14-1.29, p=0.16). Conclusions: In our study previous H. pylori eradication therapy was not associated with the onset of IBD. Whether in a subgroup of patients, H. pylori eradication therapy may trigger a latent IBD, cannot be excluded.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Crohn´s disease; Helicobacter pylori; Inflammatory bowel disease; Ulcerative colitis

Helicobacter pylori induced gastric carcinogenesis - The best molecular model we have? - Link, Alexander; Bornschein, Jan; Thon, Cosima (Best Practice & Research in Clinical Gastroenterology, 2021)
Gastric carcinogenesis can be described as a consequence of multilevel molecular alterations that is triggered by a cascade of events. Historically, diet and environmental factors have been identified to substantially contribute to carcinogenesis before the discovery of Helicobacter pylori (H. pylori). But H. pylori infection has revolutionized the understanding of gastric carcinogenesis. Although the model of H. pylori-driven carcinogenesis remains valid, there is a continuous effort to precisely delineate the molecular pathways involved and to understand the interplay with additional risk factors including recent relevant knowledge on the stomach microbiota. In this review, we provide an updated view on the models of gastric carcinogenesis. This includes historically appreciated H. pylori-induced models and expands these taking recent molecular data into consideration. Based on the data provided, we conclude that indeed H. pylori-carcinogenesis remains one of the best-established models at least for a subset of gastric cancers. Implementation of the recently identified molecular subtypes in novel genetic animal models is required to expand our knowledge on H. pylori-independent carcinogenesis.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Carcinogenesis; EBV; Gastric cancer; Helicobacter pylori; Mice; Microbiota

Helicobacter pylori infection is associated with a reduced risk of developing eosinophilic oesophagitis - Von Arnim, U.; Wex, T.; Link, Alexander; Messerschmidt, M.; Venerito, M.; Miehlke, S.; Malfertheiner, P. (Alimentary Pharmacology & Therapeutics, 2016)
Background: Eosinophilic oesophagitis (EoE) represents a chronic immune-antigen-mediated allergic disease of the oesophagus of still unknown aetiology. Environmental exposure has been postulated to play a pathogenetic role. Helicobacter pylori (H. pylori) infection has been inversely associated with allergic diseases including atopic dermatitis, asthma and allergic rhinitis and H. pylori may play a protective role in these conditions. Little is known about the relationship between EoE and H. pylori. Aim: To investigate in a case-control study whether H. pylori infection is associated with a reduced risk of developing EoE. Methods: H. pylori infection was evaluated by serology in 58 [11(19%) female, 47 (81%) male, median age: 36.5 years, range 20-72 years] patients with a clinical and histologically proven diagnosis of EoE and 116 age and sex-matched controls (1 case: 2 controls). Antibodies against H. pylori were identified by enzyme-linked immunosorbent assay. Patients with H. pylori-specific IgG ≥30 enzyme immunounits were classified as H. pylori-positive. Results: 3/58 (5.2%) patients with EoE had serological evidence of H. pylori infection (EoE - H. pylori current infection) and 5/58 (8.6%) reported prior eradication therapy for H. pylori infection (EoE - H. pylori former infection). The control group demonstrated significantly higher seroprevalence of H. pylori (37.9%, P < 0.0001) when compared to patients with EoE. EoE was inversely associated with H. pylori infection [odds ratio (OR) 0.24, 95% confidence interval (CI) 0.11-0.50]. Conclusion: Helicobacter pylori infection is inversely associated with EoE. Our results may contribute to further understanding the pathogenesis and evolving aetiology of EoE.
CRIS-Team Scopus Importer:2025-10-13

Helicobacter pylori: perspectives and time trends - Malfertheiner, Peter; Link, Alexander; Selgrad, Michael (Nature Reviews Gastroenterology & Hepatology, 2014)
The discovery of Helicobacter pylori three decades ago is a modern medical success story. It markedly changed our understanding of the pathophysiology of gastroduodenal diseases and led to an improvement in the treatment of diseases related to H. pylori infection. Many of these diseases (such as ulcer disease and mucosal associated lymphoid tissue lymphoma) have become curable, and others (gastric cancer) might be preventable with the application of H. pylori eradication therapy. Since its discovery, H. pylori has also been identified as a trigger for some extragastric diseases. Promising results in this exciting field might have a clinical effect in the near future. This Timeline gives an overview of the success of clinical research on H. pylori to date and highlights some future trends in this area.
CRIS-Team Scopus Importer:2025-10-13

Helicobacter pylori serology in relation to hepatitis C virus infection and IL28B single nucleotide polymorphism - Gutwerk, Alexander; Wex, Thomas; Stein, Kerstin; Langner, Cosima; Canbay, Ali; Malfertheiner, Peter; Link, Alexander (Journal of Clinical Medicine, 2018)
The aim of the study was to evaluate the serological rate of Helicobacter pylori (H. pylori) infection in patients with chronic hepatitis C virus (HCV) infection and determine any correlations with liver damage and IL28B single-nucleotide polymorphism (SNP). One hundred eighty-nine patients with chronic HCV infection were included in the study, and H. pylori status was defined based on anti-H. pylori-IgG or anti-CagA-IgG antibodies using enzyme-linked immunosorbent assay (ELISA). Liver damage was assessed using histology or transient elastography. IL28B C/T polymorphism (rs12979860) was evaluated in circulating blood cells using a PCR-based restriction fragment length polymorphism assay. Overall H. pylori serology was positive in 38.1% of our HCV-infected subjects. Among those, the anti-CagA-IgG positivity rate was 43.1% and was within the range of previously described populations of the same region. Highest prevalence of H. pylori was found in patients between 31 and 40 years compared to other age subgroups. The seropositivity rate was higher in the non-cirrhotic group than the cirrhotic one (45.4% vs. 20.0%, p < 0.05). No difference was found in IL28B genotype between H. pylori-positive and -negative cohorts. However, we observed a trend for the lower anti-CagA-IgG expression level in relation to the IL28B T-allele. Our results do not support an association between HCV and H. pylori infection. Whether IL28B SNP has a functional role in modulation of serological response to H. pylori CagA needs further investigation.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Antibody; CagA; Cirrhosis; Helicobacter pylori; Hepatitis C virus; IL28B; Prevalence; Rs12979860; Serological rate

Helicobacter pylori vacA genotype is a predominant determinant of immune response to Helicobacter pylori CagA - Link, Alexander; Langner, Cosima; Schirrmeister, Wiebke; Habendorf, Wiebke; Weigt, Jochen; Venerito, Marino; Tammer, Ina; Schlüter, Dirk; Schlaermann, Philipp; Meyer, Thomas F.; Wex, Thomas; Malfertheiner, Peter (World Journal of Gastroenterology, 2017)
AIM To evaluate the frequency of Helicobacter pylori (H. pylori ) CagA antibodies in H. pylori infected subjects and to identify potential histopathological and bacterial factors related to H. pylori CagA-immune response. METHODS Systematic data to H. pylori isolates, blood samples, gastric biopsies for histological and molecular analyses were available from 99 prospectively recruited subjects. Serological profile (anti-H. pylori , anti-CagA) was correlated with H. pylori isolates (cagA , EPIYA, vacA s/m genotype), histology (Sydney classification) and mucosal interleukin-8 (IL-8) mRNA and protein expression. Selected H. pylori strains were assessed for H. pylori CagA protein expression and IL-8 induction in co-cultivation model with AGS cells. RESULTS Thirty point three percent of microbiologically confirmed H. pylori infected patients were seropositive for CagA. Majority of H. pylori isolates were cagA gene positive (93.9%) with following vacA polymorphisms: 42.4% vacA s1m1 , 23.2% s1m2 and 34.3% s2m2 . Anti-CagAIgG seropositivity was strongly associated with atrophic gastritis, increased mucosal inflammation according to the Sydney score, IL-8 and cagA mRNA expression. VacA s and m polymorphisms were the major determinants for positive (vacA s1m1) or negative (vacA s2m2) anti-CagA serological immune response, which also correlated with the in vitro inflammatory potential in AGS cells. In vitro co-cultivation of representative H. pylori strains with AGS cells confirmed functional CagA translocation, which showed only partial correlation with CagA seropositivity in patients, supporting vacA as major co-determinant of the immune response. CONCLUSION Serological immune response to H. pylori cagA + strain in H. pylori infected patients is strongly associated with vacA polymorphism, suggesting the crucial role of bacterial factors in immune and clinical phenotype of the infection.
CRIS-Team Scopus Importer:2025-10-13
Keywords: CagA; Helicobacter pylori; Immune response; Seropositivity; VacA; Virulence factors

Heterogeneity in strategies to maintain the teaching activities during SARS-CoV-2 pandemic - Hipler, Noam M.; Prazienka, Philipp; Wiesmann, Crispin; Dieterich, Daniela C.; Link, Alexander (Discover Education, 2023)
Introduction: During the SARS-CoV-2 pandemic, the training of medical students was severely disrupted. Government authorities imposed a second national lockdown, which lasted from December 2020 to May 2021, forcing medical schools to adapt their teaching strategies. Several surveys have assessed students’ perspectives, but there is limited data available to objectively assess and compare different strategies between medical faculties. The aim of this study was to evaluate the lecturer-based perspective to assess the impact on the theoretical and practical education of medical students before and during the second lockdown. Methods: We developed a questionnaire focusing on theoretical and practical training during pandemic before and during the second lockdown. The questionnaire was sent by personal invitation in January 2021 to all responsible lecturers of gastroenterology and hepatology departments at university hospitals in Germany. Results: The complete response rate was obtained from 52.5% (21/40) teaching centres representative of all regions in Germany. While the majority of respondents (62%) reported a limited impact of the lockdown on theoretical training, 90.5% reported a significant impact on practical training during the SARS-CoV-2 pandemic response. Several centres adapted virtual or hybrid education early during the pandemic, bedside teaching was down to 38.1% (8/21), particularly for students in the early phase of education, suggesting a substantial long-term impact on students' skills. Conclusion: Our questionnaire-based data provide one of the first systematic evaluation of faculty-based assessments of the potential impact of the pandemic during lockdown on medical education. We observed considerable heterogeneity in strategies for maintaining teaching activities during the SARS-CoV-2 pandemic in Germany.
CRIS-Team Scopus Importer:2025-10-13

Higher physical activity levels are related to faecal microbiota diversity and composition in young adults - Ortiz-Alvarez, Lourdes; Xu, Huiwen; Ruiz-Campos, Samuel; Acosta, Francisco M.; Migueles, Jairo H.; Vilchez-Vargas, Ramiro; Link, Alexander; Plaza-Díaz, Julio; Gil, Angel; Labayen, Idoia; Ruiz, Jonatan R.; Martinez-Tellez, Borja (Biology of Sport, 2025)
Increasing physical activity (PA) is recognised as an efficacious approach for preventing and treating cardiometabolic diseases. Recently, the composition of microorganisms living within the gut has been proposed as an important appropriate target for treating these diseases. Whether PA is related to faecal microbiota diversity and composition in humans remains to be ascertained. Thus, we examined the association of the time spent in objectively measured PA with faecal microbiota diversity and composition in young adults. A cross-sectional study enrolled 88 young adults aged 22.0 ± 2.3 years (72.7% women), whose time spent in PA at different intensities was objectively measured with a wrist-worn accelerometer for 7 consecutive days. Faecal microbiota diversity and composition were analysed with hypervariable tag sequencing of the V3–V4 region of the 16S rRNA gene. The mean Euclidean Norm of the raw accelerations Minus One (mg) during waking time, considered as overall PA, and the time spent in vigorous PA were positively correlated with alpha diversity indexes (all rho ≥ 0.23, P ≤ 0.034). Regarding faecal microbiota composition, participants with low time spent in vigorous PA had higher relative abundance of the Gammaproteobacteria class (q = 0.021, FDR = q-value) compared to the participants with high time spent in vigorous PA, and lower relative abundance of the Porphyromonadaceae family (q = 0.031) and the Alistipes genus (q = 0.015) compared to the individuals with high and intermediate time spent in vigorous PA, respectively. Our results suggest that PA, especially of vigorous intensity, is related to faecal microbiota diversity and the Gammaproteobacteria class and Porphyromonadaceae family in young adults.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Activity monitor; Gastrointestinal microbiome; Obesity; Physical activity; Shorts-chain fatty acids

How do international gastric cancer prevention guidelines influence clinical practice globally? - Gasenko, Evita; Leja, Marcis; Polaka, Inese; Hegmane, Alinta; Murillo, Raul; Bordin, Dmitry; Link, Alexander; Kulju, Minna; Mochalski, Pawel; Shani, Gidi; Malfertheiner, Peter; Herrero, Rolando; et al. (European Journal of Cancer Prevention, 2020)
Clinical guidelines recommend particular approaches, including 'screen-and-treat' strategy for Helicobacter pylori, to prevent gastric cancer. However, little of this is implemented in clinical practice. The aim of the study was to identify barriers to implementation of international guidelines. A web-based questionnaire distributed globally to specialists in the field. Altogether 886 responses from 75 countries were received. Of the responders, 570 (64%) were men of mean age 47 years. There were 606 gastroenterologists and 65 epidemiologists among the responders. Altogether, 79.8% of the responders disagreed that the burden of gastric cancer is a diminishing problem. 'Screen-and-treat' strategy for H. pylori in the responder's country was considered appropriate by 44.4%, inappropriate by 24.3%, with 31.3% being uncertain. Population-based screening for gastric cancer was considered appropriate in the respective home-country by 62.2%, in other areas-but not the home country-by 27.6%, and inappropriate by 10.2%. As a screening tool, upper endoscopy was acceptable by 35.6%, upper X-ray series by 55.3%, pepsinogens by 26.2% and breath-tests by 23.4%; accuracy, cost-effectiveness and feasibility among the tests varied widely. The attitude towards H. pylori vaccination was that 4.6% of the responders were eager to start vaccination immediately, 55.9% were supporting vaccination but considered that more data are required 12% were negative, and 27.6% did not have an opinion. In general, the attitude of the specialists was in line with guidelines, but was not always translated into clinical practice, particularly in the case of 'screen-and-treat' strategy.
CRIS-Team Scopus Importer:2025-10-13
Keywords: endoscopy; gastric cancer; guidelines; Helicobacter pylori; pepsinogens; prevention; screen and treat strategy; screening; survey; volatile organic compounds

Identification of long intergenic non-coding RNAs (lincRNAs) deregulated in gastrointestinal stromal tumors (GISTs) - Gyvyte, Ugne; Kupcinskas, Juozas; Juzenas, Simonas; Inciuraite, Ruta; Poskiene, Lina; Salteniene, Violeta; Link, Alexander; Fassan, Matteo; Franke, Andre; Kupcinskas, Limas; Skieceviciene, Jurgita (PLoS ONE, 2018)
Long intergenic non-coding RNAs (lincRNAs) are >200 nucleotides long non-coding RNAs, which have been shown to be implicated in carcinogenic processes by interacting with cancer associated genes or other non-coding RNAs. However, their role in development of rare gastrointestinal stromal tumors (GISTs) is barely investigated. Therefore, the aim of this study was to define lincRNAs deregulated in GIST and find new GIST-lincRNA associations. Next-generation sequencing data of paired GIST and adjacent tissue samples from 15 patients were subjected to a web-based lincRNA analysis. Three deregulated lincRNAs (MALAT1, H19 and FENDRR; adjusted p-value < 0.05) were selected for expression validation in a larger group of patients (n = 22) by RT-qPCR method. However, only H19 and FENDRR showed significant upregulation in the validation cohort (adjusted p < 0.05). Further, we performed correlation analyses between expression levels of deregulated lincRNAs and GIST-associated oncogenes or GIST deregulated microRNAs. We found high positive correlations between expression of H19 and known GIST related oncogene ETV1, and between H19 and miR-455-3p. These findings expand the knowledge on lincRNAs deregulated in GIST and may be an important resource for the future studies investigating lincRNAs functionally relevant to GIST carcinogenesis.
CRIS-Team Scopus Importer:2025-10-13

Identifying Risk Factors for Metachronous Colorectal Cancer in Lynch Syndrome - Hüneburg, Robert; Weber, Karolin; Aretz, Stefan; Steinke-Lange, Verena; Holinski-Feder, Elke; Kloor, Matthias; Redler, Silke; Vangala, Deepak B.; Schröck, Evelin; Block, Andreas; Ripperger, Tim; van Beekum, Katrin; et al. (Clinical Gastroenterology and Hepatology, 2025)
Background & Aims: Lynch syndrome (LS) is the most common hereditary colorectal cancer (CRC) syndrome. The choice of extended or partial colectomy in patients with LS with primary CRC may influence the risk of metachronous CRC. This study aimed to identify factors associated with metachronous CRC risk and evaluate their potential implications for surgical decision-making. Methods: We analyzed data from the German Consortium for Familial Intestinal Cancer of patients with LS who underwent either extended or partial colectomy for primary CRC. Cox regression models were used to assess the risk of metachronous CRC, adjusting for sex, age, tumor location, surveillance adherence, and gene. Results: Among 852 LS carriers, 21.1% developed metachronous CRC over a median follow-up of 7.9 years. Among high-risk patients with LS, partial colectomy was associated with a borderline nonsignificant increased risk of metachronous CRC of 3.78 (95% confidence interval, 0.93–15.34; P = .063) compared with extended colectomy. Male sex (hazard ratio [HR], 2.16; P < .001), older age at primary CRC diagnosis (HR, 1.03; P < .001), and left-sided tumor location (HR, 1.53; P = .037) were additional risk factors. Surveillance adherence was not significantly associated with metachronous CRC risk. Conclusions: This study identifies important risk factors for metachronous CRC in patients with LS, which may support personalized counseling regarding surgical strategies. The findings highlight the complexity of surgical decision-making and the need for individualized approaches. Further studies are required to refine risk stratification and evaluate long-term outcomes to optimize patient care.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Colorectal Cancer; Genetics; Lynch Syndrome; Metachronous CRC; Prevention

Impact of endoscopy-based research on quality of life in healthy volunteers - Link, Alexander; Treiber, Gerhard; Peters, Brigitte; Wex, Thomas; Malfertheiner, Peter (World Journal of Gastroenterology, 2010)
AIM: To study the impact of an endoscopy-based long-term study on the quality of life in healthy volunteers (HV). METHODS: Ten HV were included into a long-term prospective endoscopy-based placebo-controlled trial with 15 endoscopic examinations per person in 5 different drug phases. Participants completed short form-36 (SF-36) and visual analog scale-based questionnaires (VAS) for different abdominal symptoms at days 0, 7 and 14 of each drug phase. Analyses were performed according to short- and long-term changes and compared to the control group. RESULTS: All HV completed the study with duration of more than 6 mo. Initial quality of life score was comparable to a general population. Analyses of the SF-36 questionnaires showed no significant changes in physical, mental and total scores, either in a short-term perspective due to different medications, or to potentially endoscopic procedure-associated long-term cumulative changes. Analogous to SF-36, VAS revealed no significant changes in total scores for pathological abdominal symptoms and remained unchanged over the time course and when compared to the control population. CONCLUSION: This study demonstrates that quality of life in HV is not significantly affected by a long-term endoscopy-based study with multiple endoscopic procedures. © 2010 Baishideng. All rights reserved.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Endoscopy research; Ethics; Healthy volunteers; Quality of life

Impact of healthy aging on active bacterial assemblages throughout the gastrointestinal tract - Schütte, Kerstin; Schulz, Christian; Vilchez-Vargas, Ramiro; Vasapolli, Riccardo; Palm, Frederike; Simon, Bianca; Schomburg, Dirk; Lux, Anke; Geffers, Robert; Pieper, Dietmar H.; Link, Alexander; Malfertheiner, Peter (Gut Microbes, 2021)
The adaption of gut microbiota (GM) throughout human life is a key factor in maintaining health. Interventions to restore a healthy GM composition may have the potential to improve health and disease outcomes in the elderly. We performed a comprehensive characterization of changes in the luminal and mucosa-associated microbiota composition in elderly compared with younger healthy individuals. Samples from saliva and feces, and biopsies from the upper and lower gastrointestinal tract (UGIT, LGIT), were collected from 59 asymptomatic individuals grouped by age: 40–55, 56–70, and 71–85 years). All underwent anthropometric, geriatric, and nutritional assessment. RNA was extracted and reverse-transcribed into complementary DNA; the V1–V2 regions of 16S ribosomal RNA genes were amplified and sequenced. Abundances of the taxa in all taxonomic ranks in each sample type were used to construct sample-similarity matrices by the Bray–Curtis algorithm. Significant differences between defined groups were assessed by analysis of similarity. The bacterial community showed strong interindividual variations and a clear distinction between samples from UGIT, LGIT, and feces. While in saliva some taxa were affected by aging, this number was considerably greater in UGIT and was subsequently higher in LGIT. Unexpectedly, aging scarcely influenced the bacterial community of feces over the age range of 40–85 years. The development of interventions to preserve and restore human health with increased age by establishing a healthy gut microbiome should not rely solely on data from fecal analysis, as the intestinal mucosa is affected by more significant changes, which differ from those observed in fecal analyses.
CRIS-Team Scopus Importer:2025-10-13
Keywords: gut microbiota; Healthy aging; microbiome; nutrition; physical fitness

Induction of Secretagogue Independent Gastric Acid Secretion via a Novel Aspirin-Activated Pathway - Kitay, Alice Miriam; Ferstl, Florentina Sophie; Link, Alexander; Geibel, John Peter (Frontiers in Physiology, 2019)
Aspirin has been widely recommended for acute and chronic conditions for over 2,000 years. Either single or repetitive doses are commonly used for analgesic and antipyretic reasons and to prevent heart attacks, stroke, and blood clot formation. Recent studies show that it can also be used chronically to dramatically reduce the risk of a variety of cancers. However, prolonged usage of aspirin can cause severe damage to the mucosal barrier, increasing the risk of ulcer formation and GI-bleeding events. In the present study, we show the effects of acute low-dose aspirin exposure as an active secretagogue-inducing gastric acid secretion. Studies were carried out with isolated gastric glands using the pH-sensitive dye BCECF-AM to assess acid secretion. The non-selective NOS inhibitor L-NAME (30 μM), or the specific inhibitor ODQ (1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one) was applied while monitoring intracellular pH. The effects of basolateral exposure to aspirin (acetylsalicylic acid, ASA) caused activation of gastric acid secretion via the H+, K+-ATPase. Our data suggest that aspirin increases nitric oxide (NO) production, which in turn activates acid secretion. Exposure of gastric glands to either the non-selective NOS inhibitor L-NAME, and the highly selective, soluble guanylyl cyclase inhibitor 1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) effectively inhibited aspirin-dependent gastric acid secretion. Aspirin can be considered as a novel secretagogue, in the way that it activates the H+, K+-ATPase. With increased daily aspirin consumption, our findings have important implications for all individuals consuming aspirin even in low doses and the potential risks for increased acid secretion.
CRIS-Team Scopus Importer:2025-10-13
Keywords: H+; K+ ATPase; nitric oxide; pH; reflux; stomach

Inflammation promotes stomach epithelial defense by stimulating the secretion of antimicrobial peptides in the mucus - Vllahu, Megi; Voli, Antonia; Licursi, Valerio; Zagami, Claudia; D’Amore, Antonella; Traulsen, Jan; Woelffling, Sara; Schmid, Monika; Crickley, Robbie; Lisle, Richard; Link, Alexander; Tosco, Alessandra; et al. (Gut Microbes, 2024)
The mucus serves as a protective barrier in the gastrointestinal tract against microbial attacks. While its role extends beyond merely being a physical barrier, the extent of its active bactericidal properties remains unclear, and the mechanisms regulating these properties are not yet understood. We propose that inflammation induces epithelial cells to secrete antimicrobial peptides, transforming mucus into an active bactericidal agent. To investigate the properties of mucus, we previously developed mucosoid culture models that mimic the healthy human stomach epithelium. Similar to organoids, mucosoids are stem cell-driven cultures; however, the cells are cultivated on transwells at air–liquid interface. The epithelial cells of mucosoids form a polarized monolayer, allowing differentiation into all stomach lineages, including mucus-secreting cells. This setup facilitates the secretion and accumulation of mucus on the apical side of the mucosoids, enabling analysis of its bactericidal effects and protein composition, including antimicrobial peptides. Our findings show that TNFα, IL1β, and IFNγ induce the secretion of antimicrobials such as lactotransferrin, lipocalin2, complement component 3, and CXCL9 into the mucus. This antimicrobial-enriched mucus can partially eliminate Helicobacter pylori, a key stomach pathogen. The bactericidal activity depends on the concentration of each antimicrobial and their gene expression is higher in patients with inflammation and H.pylori-associated chronic gastritis. However, we also find that H. pylori infection can reduce the expression of antimicrobial encoding genes promoted by inflammation. These findings suggest that controlling antimicrobial secretion in the mucus is a critical component of epithelial immunity. However, pathogens like H. pylori can overcome these defenses and survive in the mucosa.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Antimicrobial peptides; Epithelial defence; Helicobacter pylori; Inflammation; Innate immunity; Mucus; Stomach

Influence of laboratory-related and endoscopy-related factors on the assessment of serum pepsinogens and gastrin-17 - Goni, Elisabetta; Venerito, Marino; Schulz, Christian; Weigt, Jochen; Langner, Cosima; Link, Alexander; Malfertheiner, Peter (European Journal of Gastroenterology & Hepatology, 2017)
Background and aim Serum pepsinogen I (PGI) and pepsinogen II (PGII) are noninvasive parameters in the detection of atrophic gastritis. The diagnostic add-on value of serum gastrin-17 (G-17) remains uncertain. The aim of this study was to assess the stability of these serum parameters over time and to evaluate the influence of clinical factors, such as upper gastrointestinal (GI) endoscopy and bowel cleansing, on serum PGI, PGII, and G-17 assessment. Patients and methods A prospective study was carried out in healthy individuals and patients. For the stability analyses, the plasma and serum samples from 23 individuals were processed at different time points with and without the addition of a stabilizer. Ten patients were included to evaluate the influence of upper GI endoscopy and 18 patients to evaluate the effect of bowel cleansing before colonoscopy. Results PGI, PGII, and G-17 levels were not statistically different in the serum and plasma. PGI and PGII serum levels were stable over time. G-17 is associated with time-dependent degradation (P=0.0001). The addition of the G-17 stabilizer showed no improvement in stability. Upper GI endoscopy and bowel preparation before colonoscopy were associated with minimal variations in PGI and PGII, whereas G-17 showed patient-specific alterations. Conclusion PGI and PGII serum levels are stable over time. However, G-17 stability is strongly dependent on the time of processing and storage; therefore, samples for G-17 analysis need to be processed no later than 6 h after blood collection. Upper GI endoscopy and colonoscopy preparation lead to minimal nonsignificant changes in basal PGI, PGII, and G-17 levels.
CRIS-Team Scopus Importer:2025-10-13
Keywords: endoscopy-related factors; gastric biomarkers; gastrin-17; pepsinogens; preanalytical factors; serum stability of gastric biomarker

Integrating a microRNA signature as a liquid biopsy-based tool for the early diagnosis and prediction of potential therapeutic targets in pancreatic cancer - Shi, Wenjie; Wartmann, Thomas; Accuffi, Sara; Al-Madhi, Sara; Perrakis, Aristotelis; Kahlert, Christoph; Link, Alexander; Venerito, Marino; Keitel-Anselmino, Verena; Bruns, Christiane; Croner, Roland S.; Zhao, Yue; et al. (British Journal of Cancer, 2024)
Introduction: Pancreatic cancer is a highly aggressive cancer, and early diagnosis significantly improves patient prognosis due to the early implementation of curative-intent surgery. Our study aimed to implement machine-learning algorithms to aid in early pancreatic cancer diagnosis based on minimally invasive liquid biopsies. Materials and methods: The analysis data were derived from nine public pancreatic cancer miRNA datasets and two sequencing datasets from 26 pancreatic cancer patients treated in our medical center, featuring small RNAseq data for patient-matched tumor and non-tumor samples and serum. Upon batch-effect removal, systematic analyses for differences between paired tissue and serum samples were performed. The robust rank aggregation (RRA) algorithm was used to reveal feature markers that were co-expressed by both sample types. The repeatability and real-world significance of the enriched markers were then determined by validating their expression in our patients’ serum. The top candidate markers were used to assess the accuracy of predicting pancreatic cancer through four machine learning methods. Notably, these markers were also applied for the identification of pancreatic cancer and pancreatitis. Finally, we explored the clinical prognostic value, candidate targets and predict possible regulatory cell biology mechanisms involved. Results: Our multicenter analysis identified hsa-miR-1246, hsa-miR-205-5p, and hsa-miR-191-5p as promising candidate serum biomarkers to identify pancreatic cancer. In the test dataset, the accuracy values of the prediction model applied via four methods were 94.4%, 84.9%, 82.3%, and 83.3%, respectively. In the real-world study, the accuracy values of this miRNA signatures were 82.3%, 83.5%, 79.0%, and 82.2. Moreover, elevated levels of these miRNAs were significant indicators of advanced disease stage and allowed the discrimination of pancreatitis from pancreatic cancer with an accuracy rate of 91.5%. Elevated expression of hsa-miR-205-5p, a previously undescribed blood marker for pancreatic cancer, is associated with negative clinical outcomes in patients. Conclusion: A panel of three miRNAs was developed with satisfactory statistical and computational performance in real-world data. Circulating hsa-miRNA 205-5p serum levels serve as a minimally invasive, early detection tool for pancreatic cancer diagnosis and disease staging and might help monitor therapy success. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2025-10-13

International consensus statement on microbiome testing in clinical practice - Porcari, Serena; Mullish, Benjamin H.; Asnicar, Francesco; Ng, Siew C.; Zhao, Liping; Hansen, Richard; O'Toole, Paul W.; Raes, Jeroen; Hold, Georgina; Putignani, Lorenza; Hvas, Christian Lodberg; Zeller, Georg; et al. (Lancet Gastroenterology and Hepatology, 2025)
There is growing interest in the potential exploitation of the gut microbiome as a diagnostic tool in medicine, but evidence supporting its clinical usefulness is scarce. An increasing number of commercial providers offer direct-to-consumer microbiome diagnostic tests without any consensus on their regulation or any proven value in clinical practice, which could result in considerable waste of individual and health-care resources and potential drawbacks in the clinical management of patients. We convened an international multidisciplinary expert panel to standardise best practices of microbiome testing for clinical implementation, including recommendations on general principles and minimum requirements for their provision, indications, pre-testing protocols, method of analyses, reporting of results, and potential clinical value. We also evaluated current knowledge gaps and future directions in this field. We aimed to establish a framework to regulate the provision of microbiome testing and minimise the use of inappropriate tests and pave the way for the evidence-based development and use of human microbiome diagnostics in clinical medicine.
CRIS-Team Scopus Importer:2025-10-13

LINE-1 hypomethylation is not a common event in preneoplastic stages of gastric carcinogenesis - Kupcinskas, Juozas; Steponaitiene, Ruta; Langner, Cosima; Smailyte, Giedre; Skieceviciene, Jurgita; Kupcinskas, Limas; Malfertheiner, Peter; Link, Alexander (Scientific Reports, 2017)
LINE-1 hypomethylation is widely accepted as marker for global genomic DNA hypomethylation, which is a frequent event in cancer. The aim of the study was to evaluate LINE-1 methylation status at different stages of gastric carcinogenesis and evaluate its prognostic potential in clinical settings. LINE-1 methylation was analyzed in 267 tissue samples by bisulfite pyrosequencing including primary colorectal cancer tissues (T-CRC) with corresponding adjacent colon mucosa (N-CRC), gastric cancer tissues (T-GC) with corresponding gastric mucosa (N-GC), normal gastric tissues (N), chronic non-atrophic and atrophic gastritis (CG). LINE-1 methylation level was lower in both T-GC and T-CRC when compared to paired adjacent tissues. No difference was observed for LINE-1 methylation status between patients with normal gastric mucosa, CG and N-GC. LINE-1 methylation in T-GC but not N-GC tended to correlate with age. Subgroup stratification analysis did not reveal significant differences in LINE-1 methylation status according to tumor stage, anatomical location, histological subtype, differentiation grade. We observed similar overall survival data between patients with high or low LINE-1 levels. In summary, LINE-1 hypomethylation is a characteristic feature in GC but not very common in early preneoplastic stages of gastric carcinogenesis. Prognostic role of LINE-1 hypomethylation in GC patients could not be confirmed in this cohort.
CRIS-Team Scopus Importer:2025-10-13

Lipoprotein and Metabolic Profiles Indicate Similar Cardiovascular Risk of Liver Steatosis and NASH - Gottlieb, Aline; Leven, Anna Sophia; Sowa, Jan Peter; Borucki, Katrin; Link, Alexander; Yilmaz, Elvan; Aygen, Sitke; Canbay, Ali; Porsch-Özcürümez, Mustafa (Digestion, 2021)
Background and Aim: Nonalcoholic fatty liver disease (NAFLD) affects about 25% of the global population, with no reliable noninvasive tests to diagnose nonalcoholic steatohepatitis (NASH) and to differentiate between NASH and nonalcoholic fatty liver (NAFL) (steatosis alone). It is unclear if NAFL and NASH differ in cardiovascular risk for patients. Here, we compared obese NAFLD patients with a healthy cohort to test whether cholesterol compounds could represent potential noninvasive markers and to estimate associated risks. Method: Serum samples of 46 patients with histologically confirmed NAFLD (17 NAFL, 29 NASH) who underwent bariatric surgery were compared to 32 (9 males, 21 females) healthy controls (HCs). We analyzed epidemiological data, liver enzymes, cholesterol and lipid profile, and amino acids. The latter were analyzed by nuclear magnetic resonance spectroscopy. Results: Total serum and high-density lipoprotein (HDL) cholesterol were significantly lower in the NAFLD group than in HCs, with a stronger reduction in NASH. Similar observations were made for sub-specification of HDL-p, HDL-s, SHDL-p, and LHDL-p cholesterols. Low-density lipoprotein (LDL)-s and LLDL-p cholesterol were significantly reduced in NAFLD groups. Interestingly, SLDL-p cholesterol was significantly higher in the NAFL group with a stronger elevation in NASH than in HCs. The amino acids alanine, leucin, and isoleucine were significantly higher in the NAFL and NASH groups than in HCs. Conclusion: We show in this study that cholesterol profiles, apolipoproteins, and amino acids could function as a potential noninvasive test to screen for NAFLD or even NASH in larger populations. However, few differences in cholesterol profiles were identified between the NAFL and NASH groups, indicating similar cardiovascular risk profiles.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Amino acids; Cholesterol; NMR analysis; Nonalcoholic fatty liver disease; Noninvasive test

Low-dose aspirin has no impact on systemic level of serine protease inhibitors in healthy volunteers - Wex, Thomas; Treiber, Gerhard; Link, Alexander; Wex, Heike; Malfertheiner, Peter (Translational Research, 2009)
Low-dose aspirin (100 mg/day) was recently found to increase serum levels of alpha-1 protease inhibitor (A1-PI). Here, we studied the serum levels of 2 major serine protease inhibitors, A1-PI and serine leukocyte protease inhibitor (SLPI), in 10 Helicobacter pylorinegative healthy volunteers (HVs) treated with low-dose aspirin alone and in combination with other drugs.1 Neither the treatment with low-dose aspirin alone or in combination altered serum levels of both serine protease inhibitors. The previously described increase of A1-PI levels by low-dose aspirin was most likely caused by multiple endoscopies within a few days, which caused a systemic stress response. © 2009 Mosby, Inc. All rights reserved.
CRIS-Team Scopus Importer:2025-10-13

Macro-role of MicroRNA in gastric cancer - Link, Alexander; Kupcinskas, Juozas; Wex, Thomas; Malfertheiner, Peter (Digestive Diseases, 2012)
Gastric cancer is a heterogeneous disease with currently still unknown mechanisms of development. Besides genetic and epigenetic mechanisms, microRNAs (miRNAs) have recently been discovered as one of the crucial players in gastric carcinogenesis through posttranscriptional regulation of tumor suppressor and oncogenes. A substantial number of deregulated miRNAs have been revealed in gastric cancer and the biological significance of those miRNAs has been confirmed in multiple functional experiments. A growing number of studies suggest involvement of miRNAs in various steps of gastric carcinogenesis: from gastritis toward metastatic disease. Great biological stability of miRNAs opens novel fields in biomarker research with potential clinical implementation in screening, diagnosis, prediction of prognosis and therapeutic management. In this review, we provide the basic knowledge of miRNA biogenesis and discuss extensively the role of miRNAs in gastric carcinogenesis, including Helicobacter pylori-related miRNA alterations and potential translational clinical implementations. Copyright © 2012 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biomarker; Cancer; Gastric cancer; Helicobacter pylori; MicroRNA; Single nucleotide polymorphisms; Stomach

Management of epithelial precancerous conditions and early neoplasia of the stomach (MAPS III): European Society of Gastrointestinal Endoscopy (ESGE), European Helicobacter and Microbiota Study Group (EHMSG) and European Society of Pathology (ESP) Guideline update 2025 - Dinis-Ribeiro, Mário; Libânio, Diogo; Uchima, Hugo; Spaander, Manon C.W.; Bornschein, Jan; Matysiak-Budnik, Tamara; Tziatzios, Georgios; Santos-Antunes, João; Areia, Miguel; Chapelle, Nicolas; Esposito, Gianluca; Fernandez-Esparrach, Gloria; et al. (Endoscopy, 2025)
Main Recommendations At a population level, the European Society of Gastrointestinal Endoscopy (ESGE), the European Helicobacter and Microbiota Study Group (EHMSG), and the European Society of Pathology (ESP) suggest endoscopic screening for gastric cancer (and precancerous conditions) in high-risk regions (age-standardized rate [ASR] > 20 per 100 000 person-years) every 2 to 3 years or, if cost-effectiveness has been proven, in intermediate risk regions (ASR 10-20 per 100 000 person-years) every 5 years, but not in low-risk regions (ASR < 10). ESGE/EHMSG/ESP recommend that irrespective of country of origin, individual gastric risk assessment and stratification of precancerous conditions is recommended for first-time gastroscopy.ESGE/EHMSG/ESP suggest that gastric cancer screening or surveillance in asymptomatic individuals over 80 should be discontinued or not started, and that patients' comorbidities should be considered when treatment of superficial lesions is planned.ESGE/EHMSG/ESP recommend that a high quality endoscopy including the use of virtual chromoendoscopy (VCE), after proper training, is performed for screening, diagnosis, and staging of precancerous conditions (atrophy and intestinal metaplasia) and lesions (dysplasia or cancer), as well as after endoscopic therapy. VCE should be used to guide the sampling site for biopsies in the case of suspected neoplastic lesions as well as to guide biopsies for diagnosis and staging of gastric precancerous conditions, with random biopsies to be taken in the absence of endoscopically suspected changes. When there is a suspected early gastric neoplastic lesion, it should be properly described (location, size, Paris classification, vascular and mucosal pattern), photodocumented, and two targeted biopsies taken.ESGE/EHMSG/ESP do not recommend routine performance of endoscopic ultrasonography (EUS), computed tomography (CT), magnetic resonance imaging (MRI), or positron emission tomography (PET)-CT prior to endoscopic resection unless there are signs of deep submucosal invasion or if the lesion is not considered suitable for endoscopic resection.ESGE/EHMSG/ESP recommend endoscopic submucosal dissection (ESD) for differentiated gastric lesions clinically staged as dysplastic (low grade and high grade) or as intramucosal carcinoma (of any size if not ulcerated or ≤ 30 mm if ulcerated), with EMR being an alternative for Paris 0-IIa lesions of size ≤ 10 mm with low likelihood of malignancy.ESGE/EHMSG/ESP suggest that a decision about ESD can be considered for malignant lesions clinically staged as having minimal submucosal invasion if differentiated and ≤ 30 mm; or for malignant lesions clinically staged as intramucosal, undifferentiated and ≤ 20 mm; and in both cases with no ulcerative findings.ESGE/EHMSG/ESP recommends patient management based on the following histological risk after endoscopic resection: Curative/very low-risk resection (lymph node metastasis [LNM] risk < 0.5 %-1 %): en bloc R0 resection; dysplastic/pT1a, differentiated lesion, no lymphovascular invasion, independent of size if no ulceration and ≤ 30 mm if ulcerated. No further staging procedure or treatment is recommended. C urative/low-risk resection (LNM risk < 3 %): en bloc R0 resection; lesion with no lymphovascular invasion and: a) pT1b, invasion ≤ 500 μm, differentiated, size ≤ 30 mm; or b) pT1a, undifferentiated, size ≤ 20 mm and no ulceration. Staging should be completed, and further treatment is generally not necessary, but a multidisciplinary discussion is required. Local-risk resection (very low risk of LNM but increased risk of local persistence/recurrence): Piecemeal resection or tumor-positive horizontal margin of a lesion otherwise meeting curative/very low-risk criteria (or meeting low-risk criteria provided that there is no submucosal invasive tumor at the resection margin in the case of piecemeal resection or tumor-positive horizontal margin for pT1b lesions [invasion ≤ 500 μm; well-differentiated; size ≤ 30 mm, and VM0]). Endoscopic surveillance/re-treatment is recommended rather than other additional treatment. High-risk resection (noncurative): Any lesion with any of the following: (a) a positive vertical margin (if carcinoma) or lymphovascular invasion or deep submucosal invasion (> 500 μm from the muscularis mucosae); (b) poorly differentiated lesions if ulceration or size > 20 mm; (c) pT1b differentiated lesions with submucosal invasion ≤ 500 μm with size > 30 mm; or (d) intramucosal ulcerative lesion with size > 30 mm. Complete staging and strong consideration for additional treatments (surgery) in multidisciplinary discussion. ESGE/EHMSG/ESP suggest the use of validated endoscopic classifications of atrophy (e. g. Kimura-Takemoto) or intestinal metaplasia (e. g. endoscopic grading of gastric intestinal metaplasia [EGGIM]) to endoscopically stage precancerous conditions and stratify the risk for gastric cancer.ESGE/EHMSG/ESP recommend that biopsies should be taken from at least two topographic sites (2 biopsies from the antrum/incisura and 2 from the corpus, guided by VCE) in two separate, clearly labeled vials. Additional biopsy from the incisura is optional.ESGE/EHMSG/ESP recommend that patients with extensive endoscopic changes (Kimura C3 + or EGGIM 5 +) or advanced histological stages of atrophic gastritis (severe atrophic changes or intestinal metaplasia, or changes in both antrum and corpus, operative link on gastritis assessment/operative link on gastric intestinal metaplasia [OLGA/OLGIM] III/IV) should be followed up with high quality endoscopy every 3 years, irrespective of the individual's country of origin. ESGE/EHMSG/ESP recommend that no surveillance is proposed for patients with mild to moderate atrophy or intestinal metaplasia restricted to the antrum, in the absence of endoscopic signs of extensive lesions or other risk factors (family history, incomplete intestinal metaplasia, persistent H. pylori infection). This group constitutes most individuals found in clinical practice. ESGE/EHMSG/ESP recommend H. pylori eradication for patients with precancerous conditions and after endoscopic or surgical therapy. ESGE/EHMSG/ESP recommend that patients should be advised to stop smoking and low-dose daily aspirin use may be considered for the prevention of gastric cancer in selected individuals with high risk for cardiovascular events.
CRIS-Team Scopus Importer:2025-10-13

Microbial composition of tumorous and adjacent gastric tissue is associated with prognosis of gastric cancer - Lehr, Konrad; Nikitina, Darja; Vilchez-Vargas, Ramiro; Steponaitiene, Ruta; Thon, Cosima; Skieceviciene, Jurgita; Schanze, Denny; Zenker, Martin; Malfertheiner, Peter; Kupcinskas, Juozas; Link, Alexander (Scientific Reports, 2023)
Helicobacter pylori (H. pylori) infection has been considered as the main causal factor in gastric carcinogenesis, but other bacterial species may also play an important role in pathophysiology of gastric cancer. The aim of the study was to explore the link between gastric cancer prognosis and the mucosal microbial community in tumorous and adjacent gastric tissue. The bacterial profile was analysed using 16S sequencing (V1–V2 region). Microbial differences were mostly characterized by lower relative abundances of H. pylori in tumorous gastric tissues. Bacterial community and outcome data analysis revealed the genus Fusobacterium and Prevotella significantly associated with worse overall survival in gastric cancer patients. In particular, Fusobacterium was associated with significant increase in hazard ratio in both univariable and multivariable analysis and independently validated using TCMA data. Phylogenetic biodiversity of Fusobacterium species in the stomach revealed F. periodonticum as the most prevalent in healthy subjects, while F. nucleatum was most abundant in patients with gastric cancer. Bacterial community network analysis in gastric cancer suggests substantial complexity and a strong interplay between F. nucleatum and Prevotella. In summary, mucosal microbial community in the stomach was associated with worse overall survival in gastric cancer patients. Strongest negative impact on prognosis was linked to the abundance of F. nucleatum in tumorous specimens, suggesting its translational relevance in management of gastric cancer patients.
CRIS-Team Scopus Importer:2025-10-13

MicroRNA in Gastrointestinal Cancer. A Step Closer to Reality. - Link, Alexander; Goel, Ajay (Academic Press Inc., 2013)
Despite significant strides in understanding molecular pathogenesis of cancer, gastrointestinal malignancy (gastric, colorectal, pancreatic, and liver) still ranks among the leading causes of cancer-related mortality and morbidity worldwide. One of the key clinical challenges in effectively reducing disease burden associated with gastrointestinal neoplasia stems from late diagnosis, underscoring the need for early detection, risk assessment, and intervention. Currently available screening approaches are inadequate, and the development of accurate noninvasive molecular biomarkers is very much needed. microRNAs (miRNAs) are short (20-24 nucleotides in length) noncoding RNAs that have emerged as important translational gene regulators in cancer cells. In contrast to genetic markers, miRNAs have a cancer-specific expression pattern. They are present in a remarkably stable form and can be detected in a wide variety of body fluids including blood and feces. These properties make them attractive cancer biomarker targets. Although development of miRNA biomarkers is still in its early stages, burgeoning evidence supports their potential use for development as markers for early detection, prognosis, and prediction of disease recurrence and therapeutic outcome in gastrointestinal cancers. In the future, it is likely that miRNA biomarkers will revolutionize personalized medicine and mitigate disease burden associated with gastrointestinal cancers. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biomarker; Cancer; Colorectal cancer; DNA methylation; Epigenetics; Fecal; Gastric cancer; Gastrointestinal cancer; Hepatocellular carcinoma; MicroRNA; MiRNA; Noninvasive; Pancreatic cancer; Plasma; Serum

MicroRNA miR-J1-5p as a potential biomarker for JC virus infection in the gastrointestinal tract - Link, Alexander; Balaguer, Francesc; Nagasaka, Takeshi; Boland, C. Richard; Goel, Ajay (PLoS ONE, 2014)
Introduction: JC virus (JCV), a human polyomavirus that causes progressive multifocal leukoencephalopathy (PML), has been linked to colorectal cancer (CRC). However, determination of JCV infection and its role in carcinogenesis has been challenging, highlighting the need for better diagnostic strategies for this virus. JCV-specific microRNAs (miRNAs) were identified and shown to negatively regulate oncogenic JCV T-Ag. Herein, we determined the pattern of JCV miRNA expression in clinical specimens from healthy subjects and CRC patients. Material and Methods: JCV miRNA expression was validated in CRC cell lines transfected with the JCV T-Ag. Results were confirmed using CRC tissues that were expressed T-Ag. Expression of JCV-specific miR-J1-5p was measured in fresh stool samples from healthy volunteers, and samples from fecal occult blood test kits from healthy subject, and patients with colorectal neoplasms. Results: JCV miR-J1-5p was detected in JCV-transfected, but not vector-transfected, CRC cells, and was stable between cell passages. MiR-J1-5p was present in all six JCV T-Ag+ CRC samples. Surprisingly, JCV miRNA was detectable in all normal tissues, but the expression was much lower in CRC tissues. Similarly, miR-J1-5p expression was present in all fecal samples, but expression was lower in CRCs compared to controls or adenoma patients. Conclusion: JC virus-specific miR-J1-5p miRNA is a potential biomarker for viral infection, and the lower expression in patients with colonic neoplasia highlights its biological role regulating oncogenic T-Ag expression in CRC. Impact: JCV-specific miRNA is a candidate for the development of a non-invasive screening test, as well as therapeutic intervention for JCV-associated diseases. © 2014 Link et al.
CRIS-Team Scopus Importer:2025-10-13

MicroRNAs as non-invasive diagnostic biomarkers for gastric cancer: Current insights and future perspectives - Link, Alexander; Kupcinskas, Juozas (World Journal of Gastroenterology, 2018)
Non-invasive diagnostic biomarkers may contribute to an early identification of gastric cancer (GC) and improve the clinical management. Unfortunately, no sensitive and specific screening biomarkers are available yet and the currently available approaches are limited by the nature of the disease. GC is a heterogenic disease with various distinct genetic and epigenetic events that occur during the multifactorial cascade of carcinogenesis. MicroRNAs (miRNAs) are commonly deregulated in gastric mucosa during the Helicobacter pylori infection and in stepwise manner from chronic gastritis, through preneoplastic conditions such as atrophic gastritis and intestinal metaplasia, to early dysplasia and invasive cancer. Identification of miRNAs in blood in 2008 led to a great interest on miRNA-based diagnostic, prognostic biomarkers in GC. In this review, we provide the most recent systematic review on the existing studies related to miRNAs as diagnostic biomarkers for GC. Here, we systematically evaluate 75 studies related to differential expression of circulating miRNAs in GC patients and provide novel view on various heterogenic aspects of the existing data and summarize the methodological differences. Finally, we highlight several important aspects crucial to improve the future translational and clinical research in the field.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biomarkers; Blood; Gastric cancer; MicroRNA; Plasma; Screening; Serum; Stomach; Systematic review

Minimising the risk of monkeypox virus transmission during faecal microbiota transplantation: recommendations from a European expert panel - Ianiro, Gianluca; Mullish, Benjamin H.; Iqbal, Tariq H.; Terveer, Elisabeth M.; Baunwall, Simon Mark Dahl; Link, Alexander; Sokol, Harry; Kupcinskas, Juozas; Masucci, Luca; Sanguinetti, Maurizio; Vehreschild, Maria J.G.T.; Hvas, Christian L.; et al. (Lancet Gastroenterology and Hepatology, 2022)
CRIS-Team Scopus Importer:2025-10-13

Mir-20b and mir-451a are involved in gastric carcinogenesis through the PI3K/AKT/mTOR signaling pathway: Data from gastric cancer patients, cell lines and ins-gas mouse model - Streleckiene, Greta; Inciuraite, Ruta; Juzenas, Simonas; Salteniene, Violeta; Steponaitiene, Ruta; Gyvyte, Ugne; Kiudelis, Gediminas; Leja, Marcis; Ruzgys, Paulius; Satkauskas, Saulius; Kupcinskiene, Eugenija; Franke, Sabine; et al. (International Journal of Molecular Sciences, 2020)
Gastric cancer (GC) is one of the most common and lethal gastrointestinal malignancies worldwide. Many studies have shown that development of GC and other malignancies is mainly driven by alterations of cellular signaling pathways. MicroRNAs (miRNAs) are small noncoding molecules that function as tumor-suppressors or oncogenes, playing an essential role in a variety of fundamental biological processes. In order to understand the functional relevance of miRNA dysregulation, studies analyzing their target genes are of major importance. Here, we chose to analyze two miRNAs, miR-20b and miR-451a, shown to be deregulated in many different malignancies, including GC. Deregulated expression of miR-20b and miR-451a was determined in GC cell lines and the INS-GAS mouse model. Using Western Blot and luciferase reporter assay we determined that miR-20b directly regulates expression of PTEN and TXNIP, and miR-451a: CAV1 and TSC1. Loss-of-function experiments revealed that down-regulation of miR-20b and upregulation of miR-451a expression exhibits an anti-tumor effect in vitro (miR-20b: reduced viability, colony formation, increased apoptosis rate, and miR-451a: reduced colony forming ability). To summarize, the present study identified that expression of miR-20b and miR-451a are deregulated in vitro and in vivo and have a tumor suppressive role in GC through regulation of the PI3K/AKT/mTOR signaling pathway.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Gastric cancer; MicroRNAs; MiR-20b; MiR-451a; PI3K/AKT/mTOR signaling pathway

MiRNA profiling of gastrointestinal stromal tumors by nextgeneration sequencing - Gyvyte, Ugne; Juzenas, Simonas; Salteniene, Violeta; Kupcinskas, Juozas; Poskiene, Lina; Kucinskas, Laimutis; Jarmalaite, Sonata; Stuopelyte, Kristina; Steponaitiene, Ruta; Hemmrich-Stanisak, Georg; Hübenthal, Matthias; Link, Alexander; et al. (Oncotarget, 2017)
Deregulation of miRNAs has been observed virtually in all major types of cancer, whereas the miRNA signature in GIST is not well characterized yet. In this study the first high-throughput miRNA profiling of 15 paired GIST and adjacent normal tissue samples was performed using small RNA-seq approach and differentially expressed miRNAs as well as isomiRNAs were defined. Highly significantly deregulated miRNAs were selected for validation by Taq-Man low-density array in replication group of 40 paired samples. Validated miRNAs were further subjected to enrichment analysis, which revealed significantly enriched KEGG pathways in the main GIST associated pathways. Further, we used an integrated analysis of miRNA-mRNA correlations for KIT and PDGFRA target genes and found a significant correlation between all of the enriched miRNAs and their target gene KIT. Results of the phenotype analysis showed miR-509-3p to be up-regulated in epithelioid and mixed cell types compared to spindle type, whereas miR-215-5p showed negative correlation with risk grade of GIST. These data reveal a detailed miRNA profile of GIST and highlight new candidates that may be important in the development of malignant disease.
CRIS-Team Scopus Importer:2025-10-13
Keywords: GIST; MicroRNA; MicroRNA profiling; Small RNA-seq

miRNome Profiling Analysis Reveals Novel Hepatocellular Carcinoma Diagnostic, Prognostic and Treatment-Related Candidate Biomarkers: Post hoc Analysis of SORAMIC Trial - Morkunas, Egidijus; Vaitkeviciute, Evelina; Inciuraite, Ruta; Kupcinskas, Juozas; Link, Alexander; Skieceviciene, Jurgita; Alunni-Fabbroni, Marianna; Schütte, Kerstin; Malfertheiner, Peter; Varkalaite, Greta; Ricke, Jens (Digestive Diseases, 2024)
Introduction: Early diagnosis of hepatocellular carcinoma (HCC) as well as evaluation of prognosis and prediction of treatment efficacy remains challenging due to the missing specific non-invasive biomarkers. The aim of this study was to identify disease-specific microRNA (miRNA) patterns for diagnosis, prediction of prognosis, and treatment response in patients with HCC. Methods: The study population included 42 HCC patients from SORAMIC clinical trial: 22 patients received sorafenib monotherapy, 20 patients underwent 90Y radioembolization in combination with sorafenib. 20 individuals were included in the control group. HCC patients underwent collection of plasma samples before and 7–9 weeks after the beginning of the treatment. Isolation of circulating miRNAs, preparation of small RNA sequencing libraries and next-generation sequencing were performed. Association analysis for novel diagnostic, prognostic, and treatment-related candidate biomarkers was performed. Results: A total of 42 differentially expressed (16 up-regulated and 26 down-regulated) miRNAs were identified comparing baseline and control group plasma samples. hsa-miR-215-5p and hsa-miR-192-5p were down-regulated, while hsa-miR-483-5p and hsa-miR-23b-3p were up-regulated comparing baseline and 7–9 weeks post-sorafenib monotherapy samples. hsa-miR-215-5p was the sole down-regulated miRNA in the same combination therapy comparison. hsa-miR-183-5p, hsa-miR-28-3p, and hsa-miR-1246 were found to be significantly up-regulated comparing non-responders versus responders to sorafenib. High hsa-miR-215-5p expression was significantly associated with worse HCC patients’ prognosis. Conclusions: Systematic miRNA profiling of highly characterized samples from SORAMIC study revealed a subset of potential miRNA biomarkers for HCC diagnosis and prognosis of sorafenib-treated patients’ survival.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Hepatocellular carcinoma; Micro RNA; Selective internal radiation therapy; Sorafenib

miRNome Profiling and Functional Analysis Reveal Involvement of hsa‐miR‐1246 in Colon Adenoma‐Carcinoma Transition by Targeting AXIN2 and CFTR - Lukosevicius, Rokas; Juzenas, Simonas; Salteniene, Violeta; Kulokiene, Ugne; Aristikyte, Justina; Hemmrich‐stanisak, Georg; Franke, Andre; Link, Alexander; Ruzgys, Paulius; Satkauskas, Saulius; Pauzas, Henrikas; Latkauskas, Tadas; et al. (International Journal of Molecular Sciences, 2022)
Regulatory changes occurring early in colorectal cancer development remain poorly investigated. Since the majority of cases develop from polyps in the adenoma‐carcinoma transition, a search of early molecular features, such as aberrations in miRNA expression occurring prior to cancer development, would enable identification of potentially causal, rather than consequential, candidates in the progression of polyp to cancer. In the current study, by employing small RNA‐seq profiling of colon biopsy samples, we described differentially expressed miRNAs and their isoforms in the adenoma‐carcinoma transition. Analysis of healthy‐adenoma‐carcinoma sequence in an independent validation group enabled us to identify early deregulated miRNAs including hsa‐miR‐ 1246 and hsa‐miR‐215‐5p, the expressions of which are, respectively, gradually increasing and decreasing. Loss‐of‐function experiments revealed that inhibition of hsa‐miR‐1246 lead to reduced cell viability, colony formation, and migration rate, thereby indicating an oncogenic effect of this miRNA in vitro. Subsequent western blot and luciferase reporter assay provided evidence of hsamiR-1246 being involved in the regulation of target AXIN2 and CFTR genes’ expression. To conclude, the present study revealed possible involvement of hsa‐miR‐1246 in early colorectal cancer development and regulation of tumor suppressors AXIN2 and CFTR.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Adenomatous polyps; Colorectal cancer; IsomiR; MicroRNA; Small RNA‐seq

MMP2 and MMP7 at the invasive front of gastric cancer are not associated with mTOR expression - Bornschein, Jan; Seidel, Tina; Langner, Cosima; Link, Alexander; Wex, Thomas; Selgrad, Michael; Jechorek, Doerthe; Meyer, Frank; Bird-Lieberman, Elizabeth; Vieth, Michael; Malfertheiner, Peter (Diagnostic Pathology, 2015)
Background: Regulation of MMP expression by activation of mTOR signalling has been demonstrated for several tumor types, but has thus far not been confirmed in gastric cancer. Findings: The study compromised 128 patients who underwent gastric resection for cancer (66.4 % male; 86 intestinal, 42 diffuse type). Immunohistochemical staining of MMPs was performed to analyse the topographical pattern of MMP expression at the tumor center and the invasive front, respectively. MMP2 showed higher expression at the invasive front compared to the tumor center, whereas MMP7 staining scores were higher in the tumor center, and there was no difference for MMP9. The expression of p-mTOR was higher in the tumor center than at the invasive front, with a similar trend for mTOR. For intestinal type gastric cancer there was a weak correlation of MMP9 with expression of mTOR in the tumor center. Otherwise, there was no correlation of the MMPs with mTOR. By treatment of MKN45 gastric cancer cells with rapamycin, a reduction of p-mTOR in the Western blot was achieved; however, expression of MMPs remained unaffected. Conclusions: Expression of MMP2 and MMP7 in gastric cancer is not associated with mTOR, MMP9 expression might be related to mTOR signalling in a subset of tumors.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Gastric cancer; MMP2; MMP7; MMP9; MTOR

Modulations in extracellular calcium lead to H+-atpase-dependent acid secretion: A clarification of PPI failure - Kitay, Alice Miriam; Schneebacher, Marie Therese; Schmitt, Anne; Heschl, Katharina; Kopic, Sascha; Alfadda, Tariq; Alsaihati, Abrar; Link, Alexander; Geibel, John Peter (American Journal of Physiology-Gastrointestinal and Liver Physiology, 2018)
The H+,K+-ATPase was identified as the primary proton secretory pathway in the gastric parietal cell and is the pharmacological target of agents suppressing acid secretion. Recently, we identified a second acid secretory protein expressed in the parietal cell, the vacuolar H+-ATPase (V-type ATPase). The aim of the present study was to further characterize H+-ATPase activation by modulations in extracellular calcium via the calcium sensing receptor (CaSR). Isolated gastric glands were loaded with the pH indicator dye BCECF-AM [2′,7′-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein acetoxymethyl ester] to measure intracellular pH. Experiments were conducted in the absence of sodium and potassium to monitor H+-ATPase-specific transport activity. CaSR was activated with the calcimimetic R568 (400 nM) and/or by modulations in extracellular Ca2+. Elevation in calcium concentrations increased proton extrusion from the gastric parietal cell. Allosteric modification of the CaSR via R568 and calcium increased vacuolar H+-ATPase activity significantly (ΔpH/minlowCa 2+ (0.1mM) = 0.001 ± 0.001, ΔpH/min normalCa 2+ (1.0mM) = 0.033 ± 0.004, ΔpH/minhighCa 2+ (5.0mM)=0.051 ± 0.005). Carbachol significantly suppressed calcium-induced gastric acid secretion via the H_-ATPase under sodium- and potassium-free conditions. We conclude that the V-type H_-ATPase is tightly linked to CaSR activation. We observed that proton pump inhibitor (PPI) exposure does not modulate H+-ATPase activity. This elevated blood calcium activation of the H+-ATPase could provide an explanation for recurrent reflux symptoms while taking a PPI therapy. NEW & NOTEWORTHY This study emphasizes the role of the H+-ATPase in acid secretion. We further demonstrate the modification of this proton excretion pathway by extracellular calcium and the activation of the calcium sensing receptor CaSR. The novelty of this paper is based on the modulation of the H+-ATPase via both extracellular Ca (activation) and the classical secretagogues histamine and carbachol (inactivation). Both activation and inactivation of this proton pump are independent of PPI modulation.
CRIS-Team Scopus Importer:2025-10-13

Molecular diagnostics in gastric cancer - Bornschein, Jan; Leja, Marcis; Kupcinskas, Juozas; Link, Alexander; Weaver, Jamie; Rugge, Massimo; Malfertheiner, Peter (Frontiers in Bioscience - Landmark, 2014)
Despite recent advances in individualised targeted therapy, gastric cancer remains one of the most challenging diseases in gastrointestinal oncology. Modern imaging techniques using endoscopic filter devices and in vivo molecular imaging are designed to enable early detection of the cancer and surveillance of patients at risk. Molecular characterisation of the tumour itself as well as of the surrounding inflammatory environment is more sophisticated in the view of tailored therapies and individual prognostic assessment. The broad application of high throughput techniques for the description of genome wide patterns of structural (copy number aberrations, single nucleotide polymorphisms, methylation pattern) and functional (gene expression profiling, proteomics, miRNA) alterations in the cancer tissue lead not only to a better understanding of the tumour biology but also to a description of gastric cancer subtypes independent from classical stratification systems. Biostatistical means are required for the interpretation of the massive amount of data generated by these approaches. In this review we give an overview on the current knowledge of diagnostic methods for detection, description and understanding of gastric cancer disease.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Array comparative genomic hybridisation; Endoscopic imaging; Gastric cancer; Her2; MiRNA; Mucins; Pepsinogens; Review

Mucin-microbiome signatures shape the tumor microenvironment in gastric cancer - Oosterlinck, Baptiste; Ceuleers, Hannah; Arras, Wout; De Man, Joris G.; Geboes, Karen; De Schepper, Heiko; Peeters, Marc; Lebeer, Sarah; Skieceviciene, Jurgita; Hold, Georgina L.; Kupcinskas, Juozas; Link, Alexander; et al. (Microbiome, 2023)
Background and aims: We aimed to identify mucin-microbiome signatures shaping the tumor microenvironment in gastric adenocarcinomas and clinical outcomes. Methods: We performed high-throughput profiling of the mucin phenotypes present in 108 gastric adenocarcinomas and 20 functional dyspepsia cases using validated mucin-based RT-qPCRs with subsequent immunohistochemistry validation and correlated the data with clinical outcome parameters. The gastric microbiota was assessed by 16S rRNA gene sequencing, taxonomy, and community composition determined, microbial networks analyzed, and the metagenome inferred in association with mucin phenotypes and expression. Results: Gastric adenocarcinomas with an intestinal mucin environment or high-level MUC13 expression are associated with poor survival. On the contrary, gastric MUC5AC or MUC6 abundance was associated with a more favorable outcome. The oral taxa Neisseria, Prevotella, and Veillonella had centralities in tumors with intestinal and mixed phenotypes and were associated with MUC13 overexpression, highlighting their role as potential drivers in MUC13 signaling in GC. Furthermore, dense bacterial networks were observed in intestinal and mixed mucin phenotype tumors whereas the lowest community complexity was shown in null mucin phenotype tumors due to higher Helicobacter abundance resulting in a more decreased diversity. Enrichment of oral or intestinal microbes was mucin phenotype dependent. More specifically, intestinal mucin phenotype tumors favored the establishment of pro-inflammatory oral taxa forming strong co-occurrence networks. Conclusions: Our results emphasize key roles for mucins in gastric cancer prognosis and shaping microbial networks in the tumor microenvironment. Specifically, the enriched oral taxa associated with aberrant MUC13 expression can be potential biomarkers in predicting disease outcomes. [MediaObject not available: see fulltext.].
CRIS-Team Scopus Importer:2025-10-13
Keywords: Microbiota; Mucin; Stomach cancer; Survival

Mucosal-associated invariant T cells from Clostridioides difficile-infected patients exhibit a distinct proinflammatory phenotype and enhanced cytotoxic activity - Brauns, Steffen; Marquardt, Isabel; Thon, Cosima; Frentzel, Sarah; Jakob, Josefine; Färber, Jacqueline; Philipsen, Lars; Jänsch, Lothar; Link, Alexander; Bruder, Dunja (International Immunology, 2023)
Mucosal-associated invariant T (MAIT) cells are innate-like T cells mainly found in the mucosa and peripheral blood. We have recently demonstrated that Clostridioides difficile activates MAIT cells in vitro. However, their role in the pathogenesis of C. difficile infection (CDI) in human patients remains elusive to date. In this study, we performed comprehensive immunophenotyping of MAIT cells derived from CDI patients and compared their phenotype to that of patients with inflammatory bowel diseases (IBD) and healthy controls. Our study revealed that blood MAIT cells from CDI patients exhibit an interleukin 17a (IL-17a)-dominated proinflammatory phenotype and an increased readiness to synthesize the proinflammatory cytokine interferon γ (IFN-γ) following in vitro re-stimulation. Moreover, the cytotoxic activity of MAIT cells, as measured by surface CD107a and intracellular granzyme B expression, was strongly increased in CDI. Multi epitope ligand cartography (MELC) analysis of intestinal biopsies from CDI patients revealed that MAIT cells exhibit an increased production of granzyme B and increased cytotoxicity compared to the control group. Together with previously published in vitro data from our group, our findings suggest that MAIT cells are functionally involved in the immune response against C. difficile and contribute to the pathogenesis of CDI.
CRIS-Team Scopus Importer:2025-10-13
Keywords: C. difficile infection; colon biopsies; immunophenotyping; inflammatory bowel disease; MELC

New Rapid Helicobacter Pylori Blood Test Based on Dual Detection of FliD and CagA Antibodies for On-Site Testing - Schulz, Christian; Kalali, Behnam; Link, Alexander; Gerhard, Markus; Malfertheiner, Peter (Clinical Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2025-10-13

Non-Invasive Markers for the Detection of Gastric Precancerous Conditions - Romańczyk, Marcin; Osmola, Malgorzata; Link, Alexander; Druet, Amaury; Hémont, Caroline; Martin, Jerome; Chapelle, Nicolas; Matysiak-Budnik, Tamara (Cancers, 2024)
Gastric cancer (GC) is still one of the most prevalent cancers worldwide, with a high mortality rate, despite improvements in diagnostic and therapeutic strategies. To diminish the GC burden, a modification of the current diagnostic paradigm, and especially endoscopic diagnosis of symptomatic individuals, is necessary. In this review article, we present a broad review and the current knowledge status on serum biomarkers, including pepsinogens, gastrin, Gastropanel®, autoantibodies, and novel biomarkers, allowing us to estimate the risk of gastric precancerous conditions (GPC)—atrophic gastritis and gastric intestinal metaplasia. The aim of the article is to emphasize the role of non-invasive testing in GC prevention. This comprehensive review describes the pathophysiological background of investigated biomarkers, their status and performance based on available data, as well as their clinical applicability. We point out future perspectives of non-invasive testing and possible new biomarkers opportunities.
CRIS-Team Scopus Importer:2025-10-13
Keywords: chronic atrophic gastritis; gastric cancer; gastric intestinal metaplasia; gastric precancerous conditions; pepsinogen

Novel application of aerobic granular biofilm systems for treating nitrate-polluted groundwater at low temperature: Microbial community and performance - Muñoz-Palazon, Barbara; Mikola, Anna; Rosa-Masegosa, Aurora; Vilchez-Vargas, Ramiro; Link, Alexander; Gonzalez-Lopez, Jesus; Gonzalez-Martinez, Alejandro (Journal of Environmental Chemical Engineering, 2022)
An aerobic granular biofilm process was operated in a sequential batch reactor for treating nitrate-pollute groundwater at 6 ºC, which was fed with a progressively reduced carbon concentration to understand the nitrate removal efficacy in cold regions by denitrifying microorganisms. The evaluation of the performance reflected a quick granulation promoted by hydraulic stress and a high organic loading rate (OLR). The granules were dense and compact and kept stable conformation until the end of operation, despite the low temperature. Nitrate removal in the stage with high OLR was close to 100%, while the stage with the lowest OLR reached efficiencies higher than 87% in steady-state, suppose a successful advantage against other biological processes for treating drinking water. The bacterial community in the mature granules were colonized by cold-adapted microorganisms such as Holophagaceae and Candidatus Microthrix. Methanospirillum and Bathyarchaeota were the most abundant archaeal phylotypes, which showed a more stable consortium and Nectriaceae and Trichosporonaceae were the most dominant fungal phylotypes for all stages. The qPCR revealed that the crucial role was played by Fungi and Bacteria, while Archaea lost abundance in granular biomass, despite extreme conditions. Aerobic granular sludge is a robust biological technology able to remove nitrate in oligotrophic waters bodies.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Aerobic granular biofilm; Biological denitrification; Groundwater nitrate-polluted; Low temperature; Microbial community; QPCR

Oxyntic gastric atrophy in Helicobacter pylori gastritis is distinct from autoimmune gastritis - Venerito, Marino; Varbanova, Mariya; Röhl, Friedrich Wilhelm; Reinhold, Dirk; Frauenschläger, Katrin; Jechorek, Doerthe; Weigt, Jochen; Link, Alexander; Malfertheiner, Peter (Journal of Clinical Pathology, 2016)
Aim To assess characteristics of oxyntic gastric atrophy (OGA) in autoimmune gastritis (AIG) compared with OGA as a consequence of Helicobacter pylori infection. Methods Patients undergoing oesophagogastroduodenoscopy from July 2011 to October 2014 were prospectively included (N=452). Gastric biopsies were obtained for histology and H. pylori testing. Serum gastrin-17 (G17), pepsinogen (PG) I, PGII and antibodies against H. pylori and cytotoxin-Associated gene A protein were determined in all patients. Antibodies against parietal cells and intrinsic factor were determined in patients with advanced (moderate to severe) OGA. Areas under the receiver operating characteristic curves (AUCs) were calculated for serum biomarkers and compared with histology. Results Overall, 34 patients (8.9%) had advanced OGA by histology (22 women, age 61±15 years). Current or past H. pylori infection and AIG were present in 14/34 and 22/34 patients, respectively. H. pylori-negative AIG patients (N=18) were more likely to have another autoimmune disease (OR 6.3; 95% CI 1.3 to 29.8), severe corpus atrophy (OR 10.1; 95% CI 1.9 to 54.1) and corpus intestinal metaplasia (OR 26.9; 95% CI 5.3 to 136.5) compared with H. pylori-positive patients with advanced OGA. Antrum atrophy was present in 39% of H. pylori-negative AIG patients. The diagnostic performance of G17, PG I and PGI/II was excellent for AIG patients (AUC=0.83, 0.95 and 0.97, respectively), but limited for H. pylori-positive patients with advanced OGA (AUC=0.62, 0.75 and 0.67, respectively). Conclusions H. pylori-negative AIG has a distinct clinical, morphological and serological phenotype compared with advanced OGA in H. pylori gastritis.
CRIS-Team Scopus Importer:2025-10-13

Perioperative Therapy of Oesophagogastric Adenocarcinoma: Mainstay and Future Directions - Bose, Katrin; Franck, Caspar; Müller, Meike N.; Canbay, Ali; Link, Alexander; Venerito, Marino (Gastroenterology Research and Practice, 2017)
Perioperative chemotherapy improves overall survival in patients with oesophagogastric adenocarcinoma (OAC) and locoregional disease. The mainstay of perioperative chemotherapy in these patients is a platinum/fluoropyrimidine combination. The phase III FLOT4 trial has shown that the FLOT triplet regimen (oxaliplatin, infusional 5-FU, and docetaxel) improves the outcome of patients with OAC and locoregional disease as compared to the ECF triplet (epirubicin, cisplatin, and infusional 5-FU). Targeted therapies have currently no role in the perioperative setting for the treatment of patients with OAC. For patients with oligometastatic disease, upfront gastrectomy followed by chemotherapy did not show any survival benefit compared with chemotherapy alone and thus should be discouraged. Whether surgery should be offered to patients with metastatic OAC achieving a systemic control after upfront chemotherapy is under scrutiny in the phase III FLOT5/Renaissance trial. After neoadjuvant treatment, lymph node status but not pathologic tumor response is an independent factor in the prediction of overall survival. Growing evidence suggests that perioperative chemotherapy may be associated with an increased mortality risk in patients with microsatellite instable (MSI)/mismatch repair-deficient (MMRD) adenocarcinoma, thus validating poor responsiveness to chemotherapy in MSI patients with locoregional disease.
CRIS-Team Scopus Importer:2025-10-13

Plasma Levels of Endocannabinoids and Their Analogues Are Related to Specific Fecal Bacterial Genera in Young Adults: Role in Gut Barrier Integrity - Ortiz-Alvarez, Lourdes; Xu, Huiwen; Di, Xinyu; Kohler, Isabelle; Osuna-Prieto, Francisco J.; Acosta, Francisco M.; Vilchez-Vargas, Ramiro; Link, Alexander; Plaza-Díaz, Julio; van der Stelt, Mario; Hankemeier, Thomas; Clemente-Postigo, Mercedes; et al. (Nutrients, 2022)
Objective: To investigate the association of plasma levels of endocannabinoids with fecal microbiota. Methods: Plasma levels of endocannabinoids, anandamide (AEA) and 2-arachidonoylglycerol (2-AG), as well as their eleven analogues, and arachidonic acid (AA), were measured using liquid chromatography-tandem mass spectrometry in 92 young adults. DNA extracted from stool samples was analyzed using 16S rRNA gene sequencing. Lipopolysaccharide levels were measured in plasma samples. Results: Plasma levels of endocannabinoids and their analogues were not related to beta or alpha diversity indexes. Plasma levels of AEA and related N-acylethanolamines correlated positively with the relative abundance of Faecalibacterium genus (all rho ≥ 0.26, p ≤ 0.012) and Akkermansia genus (all rho ≥ 0.22, p ≤ 0.036), and negatively with the relative abundance of Bilophila genus (all rho ≤ −0.23, p ≤ 0.031). Moreover, plasma levels of 2-AG and other acylglycerols correlated positively with the relative abundance of Parasutterella (all rho ≥ 0.24, p ≤ 0.020) and Odoribacter genera (all rho ≥ 0.27, p ≤ 0.011), and negatively with the relative abundance of Prevotella genus (all rho ≤ −0.24, p ≤ 0.023). In participants with high lipopolysaccharide values, the plasma levels of AEA and related N-acylethanolamines, as well as AA and 2-AG, were negatively correlated with plasma levels of lipopolysaccharide (all rho ≤ −0.24, p ≤ 0.020). Conclusion: Plasma levels of endocannabinoids and their analogues are correlated to specific fecal bacterial genera involved in maintaining gut barrier integrity in young adults. This suggests that plasma levels of endocannabinoids and their analogues may play a role in the gut barrier integrity in young adults.
CRIS-Team Scopus Importer:2025-10-13
Keywords: endocannabinoid system; gastrointestinal microbiome; gut barrier; inflammation; short-chain fatty acids

Plasma Nogo-A and placental growth factor levels are associated with portal hypertension in patients with liver cirrhosis - Gelman, Sigita; Zykus, Romanas; Petrauskas, Dalius; Salteniene, Violeta; Skieceviciene, Jurgita; Pranculis, Andrius; Kupcinskas, Limas; Kupcinskas, Juozas; Canbay, Ali; Link, Alexander (World Journal of Gastroenterology, 2019)
Background: Clinically significant portal hypertension (CSPH) and severe portal hypertension (SPH) increase the risk for decompensation and life-threatening complications in liver cirrhosis. Pathologic angiogenesis might contribute to the formation of these conditions. Placental growth factor (PlGF) and Nogo-A protein are biomarkers of pathological angiogenesis, but data on their role in liver cirrhosis and portal hypertension is scarce. Aim: To determine plasma levels of PlGF and Nogo-A in patients with liver cirrhosis, CSPH, SPH and potential to predict portal hypertension. Methods: A cohort of 122 patients with hepatitis C virus and/or alcohol-induced liver cirrhosis with characterized hepatic venous pressure gradient (HVPG) were included in the study. Demographic data, medical history, Child-Turcotte-Pugh and Model of End Stage liver disease score, clinical chemistry, liver stiffness values were recorded on the day of the procedure prior HVPG measurement. The degree of portal hypertension was determined by the invasive HVPG measurement. Nogo-A and PlGF plasma levels were evaluated using enzyme linked immunosorbent assay. The control group consisted of 30 healthy age- and sex- matched individuals. Results: Peripheral PlGF levels were higher and Nogo-A levels were lower in patients with liver cirrhosis (23.20 vs 9.85; P < 0.0001 and 2.19 vs 3.12; P = 0.004 respectively). There was a positive linear correlation between peripheral levels of PlGF and HVPG (r = 0.338, P = 0.001) and negative linear correlation between the peripheral Nogo-A levels and HVPG (r = -0.267, P = 0.007). PlGF levels were higher in CSPH and SPH (P = 0.006; P < 0.0001) whereas Nogo-A levels were lower (P = 0.01; P < 0.033). Area under the curve for the diagnosis of CSPH for PlGF was 0.68 (P = 0.003) and for Nogo-A - 0.67 (P = 0.01); for SPH 0.714 (P < 0.0001) and 0.65 (P = 0.014) respectively. PlGF levels were higher and Nogo-A levels were lower in patients with esophageal varices (P < 0.05). PlGF cut-off value of 25 pg/mL distinguished patients with CSPH at 55.7% sensitivity and 76.7% specificity; whereas Nogo-A cut-off value of 1.12 ng/mL was highly specific (93.1%) for the diagnosis of CSPH. Conclusion: Plasma PlGF levels were higher while Nogo-A levels were lower in patients with liver cirrhosis and portal hypertension. Biomarkers showed moderate predictive value in determining CSPH and SPH.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Angiogenesis; Hepatic venous pressure gradient; Liver cirrhosis; Nogo-A; Placental growth factor; Portal hypertension

Polymorphisms of microRNA target genes IL12B, INSR, CCND1 and IL10 in gastric cancer - Petkevicius, Vytenis; Salteniene, Violeta; Juzenas, Simonas; Wex, Thomas; Link, Alexander; Leja, Marcis; Steponaitiene, Ruta; Skieceviciene, Jurgita; Kupcinskas, Limas; Jonaitis, Laimas; Kiudelis, Gediminas; Malfertheiner, Peter; et al. (World Journal of Gastroenterology, 2017)
AIM To evaluate associations between miRNA target genes IL12B , INSR , CCND1 and IL10 polymorphisms and gastric cancer (GC) in European population. METHODS Gene polymorphisms were analyzed in 508 controls and 474 GC patients from 3 tertiary centers in Germany, Lithuania and Latvia. Controls were patients from the out-patient departments, who were referred for upper endoscopy because of dyspeptic symptoms and had no history of previous malignancy. Gastric cancer (GC) patients had histopathological verification of gastric adenocarcinoma. Genomic DNA was extracted using salting out method from peripheral blood mononuclear cells. IL12B T>G (rs1368439), INSR T>C (rs1051690), CCND1 A>C (rs7177) and IL10 T>C (rs3024498) SNPs were genotyped by the real-time polymerase chain reaction. Associations between gene polymorphism and GC were evaluated using multiple logistic regression analysis with adjustment for sex, age and country of birth. RESULTS We observed similar distribution of genotypes and allelic frequencies of all polymorphisms between GC patients and controls except of INSR rs1051690. The frequency of the T allele of INSR gene was significantly higher in GC patients than in controls (23.26% and 19.19% respectively, P = 0.028). CT genotype was also more prevalent in patients compared to control group (38.48% and 30.12% respectively, P < 0.021). Logistic regression analysis revealed that only one polymorphism (rs1051690 in INSR gene) was associated with increased risk of GC. Carriers of CT genotype had higher odds of GC when compared to CC genotype (OR = 1.45, 95%PI: 1.08-1.95, P = 0.01). Similar association was observed in a dominant model for INSR gene, where comparison of TT+CT vs CC genotypes showed an increased risk of GC (OR = 1.44, 95%PI: 1.08-1.90, P = 0.01). Other analyzed SNPs were not associated with the presence of GC. CONCLUSION INSR rs1051690 SNP is associated with increased risk of GC, while polymorphisms in IL12B , CCND1 and IL10 genes are not linked with the presence of GC.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Gastric Cancer; miRNA; Single-Nucleotide polymorphisms; Target Genes

Prediction of anastomotic insufficiency based on the mucosal microbiome prior to colorectal surgery: a proof-of-principle study - Lehr, Konrad; Lange, Undine Gabriele; Hipler, Noam Mathias; Vilchez-Vargas, Ramiro; Hoffmeister, Albrecht; Feisthammel, Jürgen; Buchloh, Dorina; Schanze, Denny; Zenker, Martin; Gockel, Ines; Link, Alexander; Jansen-Winkeln, Boris (Scientific Reports, 2024)
Anastomotic leakage (AL) is a potentially life-threatening complication following colorectal cancer (CRC) resection. In this study, we aimed to unravel longitudinal changes in microbial structure before, during, and after surgery and to determine if microbial alterations may be predictive for risk assessment between sufficient anastomotic healing (AS) and AL prior surgery. We analysed the microbiota of 134 colon mucosal biopsies with 16S rRNA V1-V2 gene sequencing. Samples were collected from three location sites before, during, and after surgery, and patients received antibiotics after the initial collection and during surgery. The microbial structure showed dynamic surgery-related changes at different time points. Overall bacterial diversity and the abundance of some genera such as Faecalibacterium or Alistipes decreased over time, while the genera Enterococcus and Escherichia_Shigella increased. The distribution of taxa between AS and AL revealed significant differences in the abundance of genera such as Prevotella, Faecalibacterium and Phocaeicola. In addition to Phocaeicola, Ruminococcus2 and Blautia showed significant differences in abundance between preoperative sample types. ROC analysis of the predictive value of these genera for AL revealed an AUC of 0.802 (p = 0.0013). In summary, microbial composition was associated with postoperative outcomes, and the abundance of certain genera may be predictive of postoperative complications.
CRIS-Team Scopus Importer:2025-10-13